Comparative Evaluation of Calcium Chloride and Polyethylene Glycol 400 on Drug Loading in Human Plasma-Derived Exosomes: Insights from BCS class II drug Spironolactone - Laraib Khan; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nabi Shah; Nadeem Ahmad; Hafiz Rashid Hussain; Sabeeh Mohsin; Izna Khan; Yasser Shahzad; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2027)

Drying-wetting cycles promote greater soil structure recovery after compaction more than freezing-thawing, but laboratory tests overestimate field responses - Muhammad Mohsin Nawaz; Mathieu Lamandé; Emmanuel Arthur (Soil and Tillage Research, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Assessing the influence of different post-harvest dormancy-breaking methods on the physicochemical characteristics of potato - Syed Mohsin Abbas; Raina Ijaz; Tanveer Hussain; Muhammad Nafees; Muhammad Wasim Haider; Alina-Stefania Stanciu; Ulkar İbrahimova (Postharvest Biology and Technology, 2026)

Multi-model drought index for Pakistan's croplands: A data fusion framework and comparative performance analysis - Akash Hussain; Wenting Han; Muhammad Amjad Saleem; Mubashir Ali Ghaffar; Mohsin Ijaz; Wajahat Waseem; Mahmood Hemat; Atiyyah Rafaqat (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Adaptive strategies of Tamarix aphylla in hyper-saline conditions of Cholistan Desert - Muhammad Akram; Nargis Naz; Hafiz Muhammad Mohsin Hassan; Maqbool Ahmed; Leman Aliyeva; Muhammad Yousaf Nadeem; Hind Saad Alsubaie; Sahar Anwar Almalki; Abdelrahman R. Ahmed; Abdullah R. Alanzi (The Science of Nature, 2026)

Integrating skill-based weighting and probabilistic modeling for enhanced drought index construction from GCM outputs - Mahrukh Yousaf; Zulfiqar Ali; Farman Ali; Hussnain Abbas; Sadia Qamar; Muhammad Mohsin (Meteorology and Atmospheric Physics, 2026)

PSO-Optimized Lithology-Guided Deep Learning Model for Uniaxial Compressive Strength Prediction from Well Logs - Liuyi Xiao; Hu Zheng; Muhammad Ali; Wakeel Hussain; Minyi Zhu; Sayed Muhammad Iqbal; Altaf Hussain; Mohsin Ali (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Solar radio flux F10.7 forecasting via deep learning: A hybrid approach with LSTM and GRU - Mohsin Ghaffar Ghouri; Muhammad Umair; Manzoor Ahmed Hashmani (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

CRISPR-based gene editing for antimicrobial resistance control in human medicine - Abdullah Afzal Alvi; Muzzamil Hussain; Sadia Noureen; Zahid Abbas Malik; Sidra Zahoor; Areej Jamil; Muhammad Ali Mohsin; Asad Azeem; Haseeb Javaid; Zeshan Hassan (Archives of Microbiology, 2026)

Breakthrough advances in plant stress physiology: Acinetobacter schindleri SR-5–1 mitigates wastewater-induced nutrient imbalances in linseed plants - Sherjeel Hashmat; Umer Farooq; Muhammad Tariq Javed; Anni Maryam Afzal; Mohsin Raza Bukhari (Biologia, 2026)

Adaptive flood hazard index: a probabilistic framework for flood risk assessment - Ayesah Waseem; Zulfiqar Ali; Muhammad Mohsin; Rizwan Niaz; Naim Ahmad (Acta Geophysica, 2026)

Dairy farm waste as a source of novel and globally disseminated multidrug-resistant Escherichia coli clones: A genomic and phylogeographic study - Muhammad Shoaib; Minjia Tang; Asim Munir; Muhammad Shafiq; Mashkoor Mohsin; Xuejing Zhang; Zhongyong Wu; Zhuolin He; Baocheng Hao; Shengyi Wang; Ruichao Li; Wanxia Pu (Journal of Hazardous Materials, 2026)

Cytotoxic and computational profiling of 2-mercaptobenzimidazole Mannich derivatives: structure activity relationship and carbonic anhydrase binding assessment - Muhammad Naeem; Arooj Mohsin Alvi; Muhammad Mehmmod Moin Ul Haq; Najia Shabbir; Shumaila Mehdi; Areen Khalid; Saqib Khan; Hafiz Muhammad Ahmad; Najm Ul Hassan Khan; Muhammad Nouman Arif; Hafiz Aamir Ali Kharl (Inflammopharmacology, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Harnessing the Potential of Nodule Endophytic Bacteria to Improve Soybean Growth Under Saline Conditions - Humaira Islam; Mohsin Tariq; Kashif Sattar; Tahira Yasmeen; Muhammad Abdul Rehman Rashid (Current Microbiology, 2026)

Biomedical applications of fungal-derived nanoparticles: bridging mycology and nanotechnology for next-generation therapeutics - Umer Rehman; Mohsin Ullah; Syed Mohammad Tauseeq Ali Shah; Muhammad Adnan; Ishtiaq Ahmad; Zabta Khan Shinwari (Plant Biosystems, 2026)

Factors influencing circular economy adoption in Pakistan’s construction industry - Rai Waqas Azfar; Mohsin Shah; Mughees Aslam; Muhammad Sohail Anwar Malik; Hamza Alam (Environment, Development and Sustainability, 2026)

Beyond traditional water resources reliance: unlocking Pakistan’s national water harvesting potential via analysis of opportunities and risks - Junaid Ahmad; Muhammad Mohsin Leghari; Muhammad Sajjad (Environment, Development and Sustainability, 2026)

Synergistic effects of pulsed electric field and ultrasound on microstructure and bioactive properties of fresh and old ginger juice - Zhong Han; Wenhao Xiao; Ji Ma; Muhammad Mohsin Raza; Xin-An Zeng; Muhammad Faisal Manzoor; Muhammad Talha Afraz (Journal of Food Engineering, 2026)

AACVD-derived Co-Ni alloys for the efficient electrooxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Muthumariappan Akilarasan; Muhammad Ali Ehsan; Mohsin Pasha; Maryum Ali; Muhammad Nawaz Tahir; Muhammad Bilal Khan Niazi; Wasif Farooq (Journal of Environmental Chemical Engineering, 2026)

Harnessing Chromium-Resistant Bacteria from Tannery Wastewater: Innovative In Vitro and In Silico Strategies for Bioremediation - Hiba Ashfaq; Aatif Amin; Mohsin Tassawar Cheema; Muhammad Nouman Majeed (Water, Air, & Soil Pollution, 2026)

A novel varying component gaussian mixture model for improved drought assessment based on standardized-type drought indices - Muhammad Ismail; Muhammad Mohsin (Theoretical and Applied Climatology, 2026)

Iron-Loaded Biochar Ameliorates Cadmium-Induced Phytotoxicity in Rapeseed by Modulating Cd Uptake, Nutrient Homeostasis, and Antioxidative Systems - Sumra Siddique Abbasi; Hafiz Saqib Hayat; Hua-Yi Chen; Muhammad Mohsin Altaf; Mudawi M. Nour; Afrah E. Mohammed (Journal of Soil Science and Plant Nutrition, 2026)

Comparative evaluation of carbon sequestration and climate change mitigation in commercially planted eucalyptus-based agroforestry systems in a semi-arid region - Ghulam Yasin; Muhammad Azeem Akhter; Muhammad Zubair; Muhammad Talha Imtiaz; Matoor Mohsin Gilani; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Dilnoza Sotiboldiyeva; Shafeeq Ur Rahman (Journal of Environmental Studies and Sciences, 2026)

Biochar mediated microbial responses to organic contaminants in soil environments: From mechanisms to ecological implications - Hao Zhu; Sami Ullah; Yuting Xu; Muhammad Salam; Silvia Celletti; Nadeem Iqbal; Muhammad Mohsin Raza; Babar Hussain; Palanisamy Vasudhevan (Applied Soil Ecology, 2026)

Evaluation of the hepatoprotective activity of the methanolic extract of Cotinus coggygria - Shahzad Kamran; Sairah Hafeez Kamran; Mohsin Ahmad Ghauri; Ali Raza; Muhammad Ajaib (Advances in Traditional Medicine, 2026)

Leveraging Extremophyte Adaptations as a Roadmap for Crop Design for Arid Lands - Mohsin Tanveer; Lei Wang; Hamza Tariq; Muhammad Talha Ramzan; Alisdair R. Fernie; Jaume Flexas; Sergey Shabala; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic climate change is driving a convergence of rapid soil aridification and secondary salinization that threatens to degrade over half of the world's arable land. As conventional glycophytic crops reach their physiological limits, global food security depends on decoding the evolutionary adaptations of extremophytes. This review synthesizes the functional traits and ecosystem‐level impacts of extremophytes, the native flora of these marginal environments, and evaluates their potential as a biophysical buffer against land degradation. Here, we identify two cornerstone strategies that allow these plants to thrive where others fail: (i) the precise spatiotemporal orchestration of reactive oxygen species (ROS) as critical signaling molecules for developmental plasticity; and (ii) the active recruitment of stress‐protective microbiomes via targeted exudation, effectively transforming barren soil into a functional ecosystem. We argue that integrating extremophytes into diversified agroecosystems, through intercropping, phytoremediation rotations, and circular bioeconomy models, offers quantifiable results to enhance ecosystem multifunctionality and sustainably intensify production on degrading lands. By bridging profound mechanistic discovery with ecological engineering, this perspective provides an actionable plan for translating extremophyte biology into crops capable of withstanding a drier future.

Peroxide crosslinking of UHMWPE using tea-polyphenols as anti-oxidants - Muhammad Aaqib Ishaq; Muhammad Kaleem Ullah Khalil; Qazi Muhammad Yaseen; Mohsin Hayat (Next Research, 2026)

Unveiling Morpho-Anatomical Strategies of Cenchrus Ciliaris L. for Survival under Vehicular Pollution Stress - Hafiz Muhammad Mohsin Hassan; Muhammad Akram; Imran Haider; Muhammad Altaf Nazir; Lamy Hamed; Abdullateef Al-Saeed; ElSayed A. Badr; Ahmed Ismail (Water, Air, & Soil Pollution, 2026)

Enhancing phytoextraction efficiency of king grass through foliar application of plant growth regulators under cadmium and chromium stress - Muhammad Mohsin Altaf; Xuezhi Dong; Meng Wang; Xiaoyan Sun; Dong Li; Zhiqiang Zhu (Plant Cell Reports, 2026)

Combatting vanadium toxicity in rapeseed (Brassica napus L.) via soil amendment and foliar application of calcium oxide nanoparticles: insights into physio-biochemical and antioxidant defense mechanisms - Muhammad Mohsin Altaf; Afrah E. Mohammed; Modhi O. Alotaibi; Motirh Al-Mutairi; Jun Wang (Plant Cell Reports, 2026)

Recent advances in machine/deep learning frameworks for biochar application in soil amendment and remediation - Muhammad Waqas; Mohsin Nawaz; Rongli Yang; Waseem Tariq; Muhammad Nauman Tahir; Shakeel Ahmad (Applied Soil Ecology, 2026)

A review of floating renewable energy technologies for sustainable development - Mir Murtaza Zangejo; Muhammad Ismail Jamali; Mohsin Ali Koondhar; Abdul Sattar Saand; Ibrahim Mahariq; Ezzeddine Touti (Ocean Engineering, 2026)

Comparative analysis of machine learning and neural network models for petrophysical property prediction in heterogeneous reservoirs - Zayan Khursheed; Muhammad Anas Jawaid; Muhammad Mustafa; Shaine Mohammadali Lalji; Syed Imran Ali; Mohsin Ayubi (Next Research, 2026)

Molecular mechanisms of heavy metal uptake, accumulation, and tolerance in sweet potato (Ipomoea batatas): implications for phytoremediation and food safety - Muhammad Shahid; Muhammad Mohsin Altaf; Muhammad Ahsan Altaf; Rafiq Ahmad; Kashif Khan; Cheng-cheng Si (Plant and Soil, 2026)

Optimizing GCM ensemble selection and weighted MME development for improved drought projection under global climate models simulations - Muhammad Shakeel; Zulfiqar Ali; Hussnain Abbas; Muhammad Mohsin; Mrim M. Alnfiai; Naim Ahmad; Rizwan Niaz (Natural Hazards, 2026)

Integrated GC–MS phytochemical analysis and in vivo assessment of antiarthritic activity of Curcuma zedoaria extracts - Yusra Wasti; Syeda Aroosa Mohsin; Muhammad Tahir Aqeel; Sania Atta; Nadeem ul Hassan Khan; Syeda Ayesha Farhana; Humaira Fatima; Iffat Naz (Inflammopharmacology, 2026)

Retraction Note: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2026)

Retraction Note: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2026)

A Novel Sequential Weighting and Standardisation Framework for Robust Drought Assessment Using CMIP6 Projections - Hussnain Abbas; Muhammad Shakeel; Muhammad Mohsin; Zulfiqar Ali; Amna Nazeer; Rizwan Niaz; Naim Ahmad (International Journal of Climatology, 2026)
In the era of global warming, drought remains one of the most pressing, insidious and complex climatic phenomena. Although Global Climate Models (GCMs) are indispensable for simulating past and future climate patterns, they continue to face persistent challenges in accurately characterising drought under diverse climate conditions due to inherent model uncertainties. Multi‐model ensembles (MMEs) are widely adopted to reduce these uncertainties; however, conventional MME approaches often overlook three critical aspects: (i) the independent relative contribution of individual GCMs, (ii) the influence of point‐wise value deviations and (iii) the sequential order of predictor inclusion in the analysis. Neglecting these factors can result in biassed weighting, reduced interpretability and overestimation of drought severity in subsequent assessments. This study introduces an integrated two‐stage framework, Integrated Ensemble Based on Sequential Predictor Contribution Analysis for Standardised Climate Indices (IEBSPCASCI), for future drought assessment using GCM projections, combining a novel weighting strategy with an optimised drought index formulation. In Stage 1, we propose the sequential relative impact weighting ensemble (SRIWE), a new GCM ensemble weighting scheme that accounts for point‐wise discrepancies and sequential predictor contributions with addressing multicollinearity among models; in Stage 2, we develop the Standardised Partitioned Impact Severity Drought Index (SPISDI), an optimal‐standardisation‐based index enhancing drought severity quantification under future climate scenarios. The proposed IEBSPCASCI framework is applied to 94 locations in Pakistan using 22 GCM from the Coupled Model Intercomparison Project Phase 6 (CMIP6) for the period 1950–2014. The Stage 1 weighting scheme, SRIWE, outperforms conventional MMEs, achieving the highest median and mean Kling–Gupta Efficiency (KGE) (0.2650, 0.2435) and Nash–Sutcliffe efficiency (NSE) (0.2074, 0.1075), and the lowest median and mean values of Mean Absolute Error (MAE) (12.5572, 18.027), indicating superior predictive skill and smaller errors. In stage 2, SPISDI‐based drought assessments reveal a consistent increase in drought severity and frequency in all SSP scenarios. Under SSP5‐8.5, the intensity of drought peaks markedly towards 2080–2100, signalling substantial climate‐induced risks to water resources and agriculture. Steady‐state probability analysis indicates that normal drought conditions dominate; however, extreme drought (ED) and severe drought (SD) events remain significant, with ED peaking at 2.37% (SSP2–4.5, 48 months) and SD reaching 8.6% (SSP1–2.6, 48 months). These findings underscore the urgent need for adaptive water management policies, climate‐resilient agricultural strategies and proactive drought risk governance to mitigate future socio‐economic impacts.

Retraction Note: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2026)

Retraction Note: Role of climate fund raising under fiscal balance on climate change mitigation: an analysis from Pareto optimality - Jie Ding; Ying Wang; Siqi Wang; Muhammad Mohsin (Environmental Science and Pollution Research, 2026)

Retraction notice to ‘Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward’ [Chemosphere 325 (2023) 138367] - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2026)

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Limacella bajaurensis sp. nov. (Amanitaceae), from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Dege Zheng; Dong‐Qin Dai; Muhammad Asif; Fazli Mula; Ishtiaq Ahmad; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this study, a new species, Limacella bajaurensis , from the Gaber Chena District, Bajaur Khyber Pakhtunkhwa, Pakistan, is reported. The new species is described through molecular phylogenetic analysis of combined internal transcribed spacer (ITS) and 28S datasets, as well as a comparison of its macro‐ and micromorphological characteristics with those of similar taxa. It forms a separate clade in the phylogenetic tree and is distinguished by having umbonate, plane to broadly convex, grayish reddish orange to light reddish brown and dark reddish brown at the center, and larger subglobose to broadly ellipsoid basidiospores 4.1–4.9 × 2.84–4.2 µm. A full description, illustrations, and phylogenetic analysis results of the new species are provided.

Coprinellus gregariodiguttulatus , a New Coprinoid Species from Margalla Hills, Islamabad, Pakistan - Fahim Ullah; Malka Saba; Iram Fatima; Muhammad Asif; Mohsin Ullah; Fazli Maula; Wajahat Akram; Amir Sohail (New Zealand Journal of Botany, 2026)
Coprinellus gregariodiguttulatus is described as a new species from Quaid‐i‐Azam University, Islamabad, Pakistan, based on morphological and molecular analyses. The species is distinguished by its small gray to light gray basidiomata, paraboloid to hemispherical pileus, and oblong to obovoid or rarely lemon basidiospores. Phylogenetic analysis of the internal transcribed spacer (ITS) region supports its placement within Coprinellus sect. Disseminati is a distinct lineage, closely related to but separate from other known taxa. This discovery from an underexplored region highlights the potential for uncovering further novel fungal diversity in Pakistan.

Calocybe barangensis sp. nov (Lyophyllaceae), from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Dege Zheng; Umer Rehman; Muhammad Asif; Syed Mohammad Tauseeq Ali Shah; Dong‐Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this study, we report a new taxon, Calocybe barangensis , from Barang, Bajaur District, Khyber Pakhtunkhwa, Pakistan. The species was described as new to science using molecular phylogenetic analysis of combined ITS and LSU datasets, as well as comparisons of its macro‐ and micromorphological characteristics with those of similar taxa. The new species forms a separate clade in the phylogenetic tree and differs in having small basidiomata with dark yellowish‐brown spores and large, globose to subglobose basidiospores (5.9–7.2 × 4.7–5.6 μm). A full description, illustrations, and phylogenetic analysis results of the new species are provided.

Regulation of biochemical attributes, photosynthetic pigments, and antioxidant activity in Zea mays L. for complete amelioration of heavy metal toxicity using synergistic application of arsenic-tolerant PGPR and nanoparticles - Mohsin Zafar; Humaira Yasmin; Tayyab Shafiq; Rabia Naz; Asia Nosheen; Muhammad Nadeem Hassan (Environmental Science and Pollution Research, 2026)

Growth and Phytostabilization Potential of Willow under Rare Earth Elements Exposure in Floating Treatment Wetlands - Muhammad Mohsin; Muhammad Ramzan; Edita Baltrėnaitė-Gedienė; Nicole Nawrot; Erik Kaipiainen; Fahad Rasheed; Zikria Zafar; Ewa Wojciechowska; Ari Pappinen; Suvi Kuittinen (Water, Air, & Soil Pollution, 2026)
Phytoremediation of contaminated freshwater bodies with rare earth elements (REEs) is a promising nature-based solution, but it is rarely studied. Here, we studied how efficiently willow ( Salix schwerinii: SS ) and cultivar (Klara: KL) purify water and react to three combined doses of REEs. SS and KL were subjected to increasing combined doses of REEs, specifically lanthanum (La) and neodymium (Nd), for 8 weeks in floating treatment wetlands (FTWs). The treatments included: T0 (tap water without REEs), T1 (10 µM La + 10 µM Nd), T2 (20 µM La + 20 µM Nd), and T3 (40 µM La + 40 µM Nd). The study aimed to evaluate how La and Nd affect willow growth, including height, dry biomass, and tolerance index, as well as their uptake and translocation within the roots, stems and leaves. Results showed that willow height increased over time, with significant biomass development and a noticeable allocation to stem biomass under REEs exposure. Height and biomass tolerance indices indicated that SS and KL exhibited high tolerance to REEs. The findings revealed the highest accumulation of La (25,252 μg plant −1 ) and Nd (18,252 μg plant −1 ) in the roots of SS in treatment T3. KL also showed the highest accumulation of La (16,153 μg plant −1 ) and Nd (13,209 μg plant −1 ) in roots, but in treatment T2. Moreover, SS and KL demonstrated increased translocation of La and Nd, particularly from the water solution to the roots, with minimal translocation to the leaves and stems. In SS, La and Nd removal efficiencies ranged from 56–95% and 40–74%, respectively. For KL, La removal varied from 22–90%, while Nd removal ranged from 21–68%. A considerable accumulation of nutrients such as P, K, Mg, and Ca in the willow tissues was also observed. Further research is needed to evaluate the long-term removal and recovery of REEs by willow and other perennial plants, with a primary focus on environmental factors and design of FTWs which may influence the uptake and translocation of REEs in plants.

Adaptive morphological and physiological strategies of Sporobolus ioclados in desert ecosystem - Muhammad Akram; Nargis Naz; Ummar Iqbal; Syeda Refat Sultana; Fahim Arshad; Muhammad Waheed; Muhammad Adeel Ghafar; Hafiz Muhammad Mohsin Hassan; Arslan Asghar; Abeer Hashem; Dalal Saad Alharbi; Graciela Dolores Avila-Quezada; et al. (The Science of Nature, 2026)

Tissue-specific Ca2+ profiles associated with differential Ca2+ signalling and salinity stress tolerance between quinoa and spinach - Mohsin Tanveer; Waqas ud Din Khan; Muhammad Obeid Alshaharni; Caroline Ivsic; Zhong-Hua Chen; Lei Wang; Sergey Shabala (Plant and Soil, 2026)

Adaptive Strategies of Carpet Grass to Drought: Insights from Physiological and Antioxidant Responses - Mohsin Nawaz; Samina Shabbir; Muhammad Mudassir Nazir; Muhammad Anas; Muhammed Farooq; Hu Xu; Wu Yang; Parvaiz Ahmad; Liao Li; Zhiyong Wang (Journal of Plant Growth Regulation, 2026)

Green Synthesis of a Reversible “ON-OFF-ON” Fluorescent Sensor for Fe3+ using Licorice-Derived N-Doped Carbon Dots - Zubair Akram; Anam Arshad; Mohsin Tehseen; Muhammad Mehdi; Ali Raza; Yulan Shi; Nan Wang; Sajida Noureen; Feng Yu (Journal of Fluorescence, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Convolutional autoencoders for low probability of detection constrained underwater acoustic communications - Mohsin Abrar Khan; Songzuo Liu; Muhammad Bilal; Ahmad Hassan (Ocean Engineering, 2026)

Halotolerant PGPRs attenuate salinity stress in maize through differential expression of stress-related genes and regulated Na+/K+ homeostasis - Tahira Yasmeen; Muhammad Saleem Arif; Aqeel Ahmad; Muhammad Usman; Mohsin Tariq; Waqas Haider; Afira Syrish (South African Journal of Botany, 2025)

Orange peel derived biochar assisted rGO@MoS₂ composite for visible light driven ciprofloxacin degradation and hydrogen evolution - Asim Jilani; Mohsin Raza Dustgeer; Mohammad Omaish Ansari; Alishbah Zaka; Muhammad Adil Mansoor; Ammar A. Melaibari; Hussameldin Ibrahim (Journal of Water Process Engineering, 2025)

Ameliorating CO₂ capture performance of PEI/PES hybrid membranes via integration of zeolitic imidazolate frameworks - Sadia Sagar; Aqib Riaz; Farzana Siddique; Aysha Siddiqa; Mohsin Ali; Mahnoor Asif; Muhammad Waqas Iqbal; Fawad Inam (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of Apocynum pictum and Apocynum venetum honey: identify with nutritional and health-promoting metabolites - Zeeshan Ali Buttar; Jiyun Ma; Lei Wang; Muhammad Rizwan Shoukat; Wei Ren; Li Jiang; Mohsin Tanveer (Food Chemistry, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Ethnobotanical inventory and threat assessment of medicinal plants in Lajbouk Valley, Khyber Pakhtunkhwa, Pakistan - Shaha Buddin; Syed Mukaram Shah; Muhammad Ibrahim; Mohsin Ullah; Waseem Ahmed Khattak; Muhammad Anas; Asif Kamal (Genetic Resources and Crop Evolution, 2025)

A Bayesian Network-Based Multimodal Blended Multiscalar Standardized Index for Improved Assessment of Extreme Hydrological Events - Zulfiqar Ali; Muhammad Mohsin; Sadia Qamar; Aamina Batool; Veysi Kartal (Environmental Modeling & Assessment, 2025)

In vitro and In Vivo Antimicrobial Activity of Melia Azedarach-Mediated Copper Oxide Nanoparticles Against Multidrug-Resistant Klebsiella pneumoniae - Nimra Arshad; Mohsin Tassawar Cheema; Aatif Amin; Rida Fatima; Mounir M. Bekhit; Nady K. Elbarbary; Muhammad Shafiq; Mohsin Khurshid (Current Microbiology, 2025)

Panel data insights into adoption of green technology and its economic role in shaping sustainability goals - Bin Xu; Ata Al Shraah; Siao-Yun Wei; Ali Mohsin Ba Awain; Muhammad Rafiq; Shamim Akhter; Tazeem Shahbaz (Clean Technologies and Environmental Policy, 2025)

Synergistic PMS activation by SnBi@ZrC under visible light for enhanced organic pollutant removal - Rana Mohsin Ali; Jie Wang; Tianhong Zhou; Yue Tian; Muhammad Usman; Hamza Khaliq; Muhammad Adnan; Zunaira Nasir; Ghulam Abbas Ashraf; Yusuke Yamauchi (Journal of Water Process Engineering, 2025)

Bridging the resolution gap: Machine learning for local-scale groundwater drought monitoring in Punjab, Pakistan - Fahimeh Youssefi; Shoaib Ali; Behnam Khorrami; Mohammad Mohsin Khan; Muhammad Jehanzaib; Talha Mahmood; Zhiming Han; Wu Haotian; Muhammad Faisal (Groundwater for Sustainable Development, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Detection of negative consequences of traffic on subsoil properties depends on measurement type and scale: The case of a Calcaric Chernozem - Maliheh Fouladidorhani; Mathieu Lamandé; Gerhard Moitzi; Muhammad Mohsin Nawaz; Emmanuel Arthur (Soil and Tillage Research, 2025)

Corrigendum to “Designing highly potential photocatalytic comprising silver deposited ZnO NPs with sulfurized graphitic carbon nitride (Ag/ZnO/S-g-C3N4) ternary composite” [J. Environ. Chem. Eng. 9 (2021) 104919] - Shahid Iqbal; Naveed Ahmad; Mohsin Javed; Muhammad Azam Qamar; Ali Bahadur; Shahid Ali; Zahoor Ahmad; Rana Muhammad Irfan; Guocong Liu; Muhammad Bilal Akbar; Muhammad Abdul Qayyum (Journal of Environmental Chemical Engineering, 2025)

Preventing electrolyte degradation through enhanced MnO2 deposition/dissolution in Zn−MnO2 battery using vanadium redox mediator - Mohsin Ali; Xinhua Zheng; Ruihao Luo; Muhammad Sajid; Saba Hazoor; Touqeer Ahmad; Aoun Raza; Nawab Ali Khan; Mingjie Wu; Wei Chen (Chemical Engineering Journal, 2025)

Rhodanine-benzamides as potential hits for α-amylase enzyme inhibitors and radical (DPPH and ABTS) scavengers - Samuel Attah Egu; Irfan Ali; Khalid Mohammed Khan; Sridevi Chigurupati; Urooj Qureshi; Uzma Salar; Zaheer Ul-Haq; Suliman A. Almahmoud; Shatha Ghazi Felemban; Mohsin Ali; Muhammad Taha (Molecular Diversity, 2025)

Unraveling the Biology and Integrated Management Strategies for Tobacco Beetle (Lasioderma serricorne) in Stored Tobacco: A Comprehensive Review - Ayesha Younas; Muhammad Adnan Bodlah; Yasir Niaz; Alishbah Mohsin; Aleena Kanwal; Imran Bodlah (Journal of Crop Health, 2025)

Stem cell therapy: a promising frontier in modern medicine with a comprehensive overview of their biology and potential therapeutic applications in chronic non-healing cutaneous injuries - Qadeer Ahmad; Shumaila Mehdi; Malik Hassan Mehmood; Muhammad Talha Asif; Muhammad Mohsin Ali (Inflammopharmacology, 2025)

Utilization of residues from microalgal industries for agricultural practices: A comprehensive review - Muhammad Zubair Mohsin; Ragnheiður þórarinsdóttir; Sigurður Brynjólfsson; Bing Wu (Chemosphere, 2025)

Comparative assessment of biochar and vermicompost on chromium bioavailability and stress alleviation in tomato (Solanum lycopersicum) - Jamaluddin Kabir; Muhammad Ansar Farooq; Shumaila Parvez; Aamir Alaud Din; Ghulam Abbas; Minggang Xu; Muhammad Mohsin Abrar (Journal of Soils and Sediments, 2025)

Crop Residue Management for Soil Health and Environmental Sustainability: A Comprehensive Review - Sadia Babar Baloch; Shahzaib Ali; Jaroslav Bernas; Petr Konvalina; Muhammad Naveed; Faryal Babar Baloch; Zameer Hussain Jamali; Tomáš Lošák; Hynek Roubík; Abdul Ghafoor; Mohsin Mehmood; Adnan Mustafa (Journal of Soil Science and Plant Nutrition, 2025)

Retraction Note: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2025)

Navigating soil microbiota shifts to organic pollutants: Insights into the roles of nZVI-biochar in soil ecosystem restoration - Sami Ullah; Babar Hussain; Nadeem Iqbal; Muhammad Salam; Muhammad Mohsin Raza; Shengyan Pu (Applied Soil Ecology, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

Cadmium Toxicity Affects Morpho-Physiological and Biochemical Attributes in Gladiolus grandiflorus L.: The Mitigating Roles of Exogenous Strigolactone (GR24) - Muhammad Ahsan; Muhammad Abdullah; Emanuele Radicetti; Mohamed Farouk Elsadek; Ali Bakhsh; Mateen Sajid; Mohammad Valipour; Aftab Jamal; Hera Gul; Syed Mohsin Abbas (Water, Air, & Soil Pollution, 2025)

Comparative efficacy of combined myo-inositol and D-chiro inositol versus metformin across PCOS Phenotypes: enhancing ovarian function, ovulation, and stress response in a prospective clinical trial - Meena Gul; Hina Khan; Bushra Rauf; Syed Murtaza Shah Bukhari; Ehtesham Ehtesham; Muhammad Omar Malik; Fawad Ali Shah; Fawaz E. Alanazi; Mohsin Shah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Carbapenem Resistant Serratia marcescens Harboring blaOXA-48, armA and aac(6′)-Ib-cr Genes: The First Baseline Study from Pakistan - Amna Kausar; Muhammad Sohail; Mohsin Khurshid; Hafiz Ghulam Murtaza Saleem (Current Microbiology, 2025)

Occupancy of diverse bacterial species in mungbean nodules functioning as plant biostimulants under saline conditions - Syeda Tahseen Zahra; Mohsin Tariq; Tahira Yasmeen; Asma Imran; Muhammad Jawad Asghar; Tayyaba Zahid; Temoor Ahmed (South African Journal of Botany, 2025)

Assessing the impact of risk perception on fisheries performance: a structural equation modeling approach in coastal fisheries - Muhammad Mohsin; Hengbin Yin; Ana Mehak (Frontiers in Marine Science, 2025)
Risk perception is crucial for making effective fisheries management strategies. However, this role of risk perception needs to be addressed, particularly in developing countries. Published literature documents such a scenario in the case of Pakistan, which results in a decreased economic contribution to the fisheries sector. Despite its importance, the role of risk perception in managing the fisheries sector is absent in online scientific studies. The present study strives to address this research void by analyzing survey-based data collected through snowball sampling between May 2022 and October 2024. Multivariate analysis, viz., Structure Equation Modeling (SEM), was done through Statistical Package for Social Sciences (SPSS) as well as Analysis of Moment Structures (AMOS). Cronbach’s alpha values for all constructs were above 0.6, with the highest being 0.962 for policies and regulations risk, confirming data reliability. Confirmatory Factor Analysis (CFA) indices, including Comparative Fit Index (CFI) (0.933) and Tucker-Lewis index (TLI) (0.916), indicated a good model fit, with acceptable construct reliability (CR) and Average Variance Extracted (AVE) values. SEM showed that economic risk (estimate = -0.425, p = 0.000), environmental risk (estimate = -0.251, p = 0.007), and consumption risk (estimate = -0.265, p = 0.000) negatively impacted performance, while policies and regulations risk (estimate = -0.113, p = 0.121) and infrastructure and logistics risk (estimate = -0.073, p = 0.411) were insignificant. Risk perception was a significant mediator of performance, with varying effects across Sindh and Balochistan. According to the survey participants, there is a dire need to increase levels of fisheries risk perception, which can be achieved through properly designed capacity-building and incentive-based management techniques. Furthermore, this study discusses the practical implications and limitations.

Integrative taxonomy and multigene phylogeny uncover three novel taxa of the genus Clitopilus from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Wajahat Akram; Fazli Maula; Fahim Ullah; Momal Batool; Mohsin Ullah; Irmgard Krisai-Greilhuber; Mubashar Raza (Mycological Progress, 2025)

Exploring FTAs, seafood exports, and SDGs: a gravity model analysis of Pakistan’s seafood trade with China and regional partners - Yuxiang Xia; Hengbin Yin; Muhammad Mohsin; Ana Mehak; Cai Yan (Frontiers in Marine Science, 2025)
This study examines the effects of Free Trade Agreements (FTAs) on Pakistan’s seafood exports, specifically analyzing the China-Pakistan Free Trade Agreement (CP-FTA) and its stages, CP-FTAI and CP-FTAII. Using the gravity model (GM) of trade, it empirically analyzes the dynamics of seafood trade between Pakistan and its neighboring countries, aiming to provide insights into improving trade balance and export performance. The study employs three econometric approaches—Ordinary Least Squares (OLS), Fixed Effects Model (FEM), and Pseudo Poisson Maximum Likelihood (PPML) to ensure the robustness and reliability of the findings. The results reveal that Pakistan’s seafood exports are significantly influenced by FTAs, particularly with Afghanistan, Sri Lanka, and Malaysia, while CPFTA-I shows a positive impact. However, CPFTA-II exhibit negative and insignificant relationship, indicating that external shocks, like the COVID-19 pandemic, have impacted trade dynamics. The results of this study are significantly relevant to multiple United Nations Sustainable Development Goals (SDGs). Notably, they contribute to SDG 8, which focuses on Decent Work and Economic Growth, by promoting trade-driven economic advancement. Furthermore, they support SDG 9, which pertains to Industry, Innovation, and Infrastructure, by facilitating infrastructure development through the China-Pakistan Economic Corridor (CPEC). Additionally, they align with SDG 12, which emphasizes Responsible Consumption and Production by advocating sustainable trade practices. The study recommends enhancing FTAs, improving infrastructure, and expanding trade with neighboring markets to optimize Pakistan’s seafood export potential. Policymakers should focus on strengthening trade agreements, streamlining logistics, and integrating variables like security and exchange rates to develop more resilient and sustainable trade strategies, contributing to important SDGs.

Enhancing drought projection reliability: a framework for optimal GCM selection, aggregation, and trend analysis under shared socioeconomic pathways - Muhammad Shakeel; Hussnain Abbas; Zulfiqar Ali; Muhammad Mohsin (Theoretical and Applied Climatology, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Soil amendment with Dryopteris nigropaleacea enhances natural control of Fusarium wilt by modulating morphological, biochemical, and physiological traits of tomato plants - Faisal Iqbal Jafri; Muhammad Akbar; Muhammad Zia ur Rehman; Mohsin Khurshid (Physiological and Molecular Plant Pathology, 2025)

Organic carbon and nitrogen accrual evidenced by the underpinning protection mechanisms in soil profile following contrasting 35-year fertilization regimes - Muhammad Mohsin Abrar; Muhammad Ahmed Waqas; Khalid Mehmood; Ruqin Fan; Baoku Zhou; Xingzhu Ma; Sun Nan; Jianjun Du; Minggang Xu (Journal of Environmental Management, 2025)

Modeling of ground motion data to assess the seismic features for monitoring the seismic activity - Samiya Akhtar; Muhammad Mohsin; Zulfiqar Ali (Natural Hazards, 2025)

Evaluating variogram models and kriging approaches for analyzing spatial trends in precipitation simulations from global climate models - Aamina Batool; Sufian Ahmad; Ayesha Waseem; Veysi Kartal; Zulfiqar Ali; Muhammad Mohsin (Acta Geophysica, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Exploring the diversity of scorpions in Lahore Division, Punjab: an ecological approach - Muhammad Mohsin Ahsan; Abdul Khalaq; Hafiz Muhammad Tahir; Muhammad Ismail; Muhammad Samiullah; Maira Noor; Safia Bibi (International Journal of Tropical Insect Science, 2025)

Corrigendum to “Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies” [Trends in Food Science & Technology 153 (2024) 104695] - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2025)

Enhancing phytoremediation in chamomile (Matricaria chamomilla L.) using moringa extract and zero-valent iron nanoparticles - Urooj Ansar Mughal; Mujahid Farid; Wajiha Sarfraz; Mostafa A. Abdel-Maksoud; Abdul Malik; Zaki ul Zaman Asam; Mohsin Abbas; Muhammad Zubair; Sabiha Fatima; Noreen Khalid (South African Journal of Botany, 2025)

De Novo synthesis of selenium-doped CeO2@Fe3O4 nanoparticles for improving secondary metabolite biosynthesis in Carthamus tinctorius cell suspension culture - Kamran Ashraf; Zebo Liu; Qamar uz Zaman; Muhammad Arshad; Waqas Qamar Zaman; Ali Shan; Junxiong Yu; Touseef ur Rehman; Yingping Zhuang; Meijin Guo; Ali Mohsin (Chemical Engineering Journal, 2025)

Effect of plastic fibers on OPC-based concrete in circular economy - Shehroze Ali; Suliman Khan; Muhammad Imran; Faizan Ali; Mohsin Nawaz (Innovative Infrastructure Solutions, 2025)

Synergistic anticancer effects of interleukin-21 combined with therapeutic peptides in multiple cancer cells - Muhammad Akram; Nao Akusa Fujimura; Saad Tahir; Rabia Abbas; Mohsin Ahmad Khan; Kausar Malik; Nadeem Ahmed (Biotechnology Letters, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Stripe rust resistance in historical wheat cultivars at seedling and adult plant stages and tagging effective resistance genes using molecular markers - Khawar Majeed; Muhammad Sufyan; Kainat Abbasi; Rafia Ahsan; Hadi Bux; Muhammad Zakria; Muhammad Fayyaz; Javed Iqbal Mirza; Mohsin Ali; Awais Rasheed; Zhonghu He (Journal of Plant Pathology, 2025)

Health Star Rating Labels: A systematic review and future research agenda - Muhammad Junaid Shahid Hasni; Mohsin Abdur Rehman; Nicolas Pontes; Muhammad Zafar Yaqub (Food Quality and Preference, 2025)

Revolutionizing Fingerprint Detection: Ce3+ Doped SiO2-Zr2O3:Sr2+ Nanocomposites with Enhanced Luminescence and Selectivity - Momna Qayyum; Sammia Shahid; Sana Mansoor; Muhammad Faizan; Mohsin Javed; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Salman Aloufi (Journal of Fluorescence, 2024)
Even though fingerprints remain one of the most reliable methods of identification, they are often lost during the recovery process. Accurate fingerprint recognition depends on the contrast between the ridges and substrate. On tough surfaces, such as glossy, colorful, and patterned materials, the contrast is harder to establish. Photoluminescent materials play a crucial role in forensic investigations as they enable the development of procedures that enhance image quality and increase the accuracy of findings from security institutions. Due to the strong emission in the red area at 620 nm, the use of trivalent Rare Earth ions (RE 3+ ) doped materials in this work is notable. Because of the unique properties and abundance of cerium, luminous materials based on SiO 2 -Zr 2 O 3 : Ce 3+ , Sr 2+ prepared via sol-gel technique present a more practical alternative for use in criminal investigations compared to current photonic materials. The sample was further co-doped with synthetic (Safranin-O and crystal violet) as well as organic (curcumin and lycopene) photoluminescent dyes. The nanocomposites were examined using X-ray diffraction analysis (XRD), energy-dispersive X-ray analysis (EDX), dynamic light scattering (DLS), scanning electron microscopy (SEM), and photoluminescence spectroscopy (PL). In conclusion, this work highlights the qualities critical to obtaining higher-resolution latent fingerprint images for potential forensic applications.

Regional distribution differences of antibiotics in tropical marine aquaculture area: Insights into antibiotic management and risk assessment - Xiaoyu Ren; Yongqiang Qin; Yankun Zhang; Jia Xie; Xiaoping Diao; Muhammad Mohsin Altaf (Science of The Total Environment, 2024)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

Pre-emergence herbicide selection for successful cultivation of black seed (Nigella sativa L.), psyllium (Plantago ovata Forsk), and quinoa (Chenopodium quinoa Willd.) - Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Zia Ul Mohsin; Majid Ali; Abdul Khaliq; Rana Nadeem Abbas; Muhammad Zafar Iqbal; Amar Matloob (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Reply by the authors to the letter by S. Nadarajah - Muhammad Mohsin; Salman Abbas; Muhammad Mubeen Khan (Stochastic Environmental Research and Risk Assessment, 2024)

A survey on the occurrence of papaya ringspot virus-P (PRSV-P) in Malaysia and genetic diversity assessment of the coat protein region - Norazyani Mohsin Mohsen; Muhamad Afiq Aziz; Kuganisha Thangaraja; Muhammad Azamuddeen Mohammad Nasir; Muhammad Zarul Hanifah Md. Zoqratt; Subha Bhassu; Rofina Yasmin Othman (Environmental Monitoring and Assessment, 2024)

Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2024)

Enhancing mango yield and soil health with organic and slow-release fertilizers: A multifaceted evaluation - Yangqiu Jiao; Xiaoyan Sun; Xuezhi Dong; Jing Yin; Zhidong Li; Kailu Zhang; Muhammad Mohsin Altaf; Dong Li; Zhiqiang Zhu (Science of The Total Environment, 2024)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Retraction Note: Assessing the nexus between COVID-19 pandemic–driven economic crisis and economic policy: lesson learned and challenges - Lei Chang; Muhammad Mohsin; Wasim Iqbal (Environmental Science and Pollution Research, 2024)

Artificial intelligence and its role in developing predictive prognostic models for patients with aneurysmal subarachnoid hemorrhage: A systematic review - Muhammad Mohsin Khan; Noman Shah; Muhammad Mohsin Arshad; Talal Alrabayah; Sirajeddin Belkhair (Next Research, 2024)

Harnessing Bacillus safensis as biofertilizer for sustainable drought alleviation in Brassica juncea L - Nizakat Bibi; Mohsin Khan; Fazal ur Rehman; Mahrukh; Shah Room; Muhammad Ansar Ahmad; Muhammad Iftikhar; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary (Biocatalysis and Agricultural Biotechnology, 2024)

Probabilistic modeling of extreme events involving decaying variables with an application in seismology - Muhammad Mohsin; Salman Abbas; Muhammad Mubeen Khan (Stochastic Environmental Research and Risk Assessment, 2024)

Integrative approach to mitigate chromium toxicity in soil and enhance antioxidant activities in rice (Oryza sativa L.) using magnesium–iron nanocomposite and Staphylococcus aureus strains - Muhammad Azhar Ali; Muhammad Fahad Sardar; Afzal Ahmed Dar; Mohsin Niaz; Jawad Ali; Qian Wang; Yu Zheng; Yadan Luo; Gadah Albasher; Fengmin Li (Environmental Geochemistry and Health, 2024)

Salt-Tolerant Plant Growth-Promoting Bacteria (ST-PGPB): An Effective Strategy for Sustainable Food Production - Syeda Tahseen Zahra; Mohsin Tariq; Muhammad Abdullah; Muhammad Kaleem Ullah; Abdul Rafay Rafiq; Aisha Siddique; Muhammad Shafiq Shahid; Temoor Ahmed; Imrana Jamil (Current Microbiology, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

Retraction Note: Assessing green financing with emission reduction and green economic recovery in emerging economies - Miaonan Lin; Haorong Zeng; Xin Zeng; Muhammad Mohsin; Syed Mubashar Raza (Environmental Science and Pollution Research, 2024)

Sustainable solutions: exploring risks and strategies in Pakistan’s seafood trade for marine conservation - Muhammad Mohsin; Hengbin Yin; Ana Mehak (Frontiers in Marine Science, 2024)
Global literature highlights risks in the seafood trade and suggests mitigation methods, but these issues are often overlooked in developing countries, particularly in Pakistan, due to ineffective policy implementation. This underlines the urgent need for a thorough investigation into Pakistan’s seafood trade to address its multifaceted risks and revive this agricultural sector. This study is notable for being the first to explore these uncharted risks in Pakistan’s seafood trade, which can help achieve the sustainable development goals (SDGs) of the United Nations, particularly SDG 14 (life underwater) and SDG 2 (zero hunger). Primary data were gathered from 626 respondents using snowball sampling and structured questionnaires from July 13, 2023, to December 27, 2023. The study used multi-criteria decision analysis, including fuzzy Analytic Hierarchy Process (AHP) and Importance Performance Analysis (IPA), and multivariate analysis, comprising Analysis of Moment Structures (AMOS), to analyze the data. The findings revealed that ‘environmental risks’ were the most significant, followed by ‘infrastructure and logistic risks’. The biggest sub-risk identified for managerial focus includes overfishing. Controlling overfishing is critical for ensuring marine conservation and reviving the seafood trade. Several sub-risks, like seafood prices, marketing strategies, consumer preferences, and tastes, are critical but never addressed in the regulations. Furthermore, risk perception mediates the relationship between risk management and risk performance. The survey respondents reported low-risk perception and inadequate management measures. Besides, this study expounds on ramifications, shortcomings, and areas for further research.

Low mercury risks in paddy soils across the Pakistan - Muhammad Wajahat Aslam; Bo Meng; Waqar Ali; Muhammad Mohsin Abrar; Mahmoud A. Abdelhafiz; Xinbin Feng (Science of The Total Environment, 2024)

Metabolic Engineering of Wheat for Enhanced Vitamin B6 to Combat Hidden Hunger - Samreen Mohsin; Muhammad Irfan; Kauser Abdulla Malik; Asma Maqbool (Plant Molecular Biology Reporter, 2024)

Role of ERG11 and MDR1 genes in cycloheximide and multidrug resistance in Candida species - Zill-e- Huma; Sidrah Saleem; Muhammad Imran; Syed Mohsin Raza; Kokab Jabeen; Faiqa Arshad (Brazilian Journal of Microbiology, 2024)

Solar light driven degradation of piroxicam and paracetamol by heterogeneous photocatalytic fenton system: Process optimization, mechanistic studies and toxicity assessment - Muhammad Mohsin; Nazia Yaqoob; Shagufta Kamal; Saima Rehman (Chemosphere, 2024)

Resources policy from extraction to innovation: The interplay of minerals, geothermal energy, technological advancements, and ecological footprint in high-ecological footprint economies - Muhammad Adnan Bashir; Li Qing; Qasim Raza Syed; Anna Barwińska-Małajowicz; Shabir Mohsin Hashmi (Resources Policy, 2024)

Assessing the generalization of forecasting ability of machine learning and probabilistic models for complex climate characteristics - Aamina Batool; Zulfiqar Ali; Muhammad Mohsin; Atef Masmoudi; Veysi Kartal; Samina Satti (Stochastic Environmental Research and Risk Assessment, 2024)

Insight into mechanism of excellent visible-light photocatalytic activity of CuO/MgO/ZnO nanocomposite for advanced solution of environmental remediation - Muhammad Imran; Mohsin Raza; Hadia Noor; Sadia Muniza Faraz; Ali Raza; Umar Farooq; Mohammad Ehtisham Khan; Syed Kashif Ali; Omer Y. Bakather; Wahid Ali; Abdullateef H. Bashiri; Waleed Zakri (Chemosphere, 2024)

Silicon oxide nanoparticle mitigated the vanadium toxicity in Cucumber (Cucumis sativus L.) - Muhammad Mohsin Altaf; Sahrish Ashraf; Muhammad Qaisar Naeem Khan; Sibgha Noreen; Muhammad Anwar; Rafa Almeer; Rattandeep Singh; Atique ur Rehman (South African Journal of Botany, 2024)

Melatonin induced reversibility of vanadium toxicity in muskmelon by regulating antioxidant defense and glyoxalase systems - Muhammad Mohsin Altaf; Zoia Arshad Awan; Sahrish Ashraf; Muhammad Ahsan Altaf; Zhiqiang Zhu; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Hazardous Materials, 2024)

Application of SUMO fusion technology for the enhancement of stability and activity of lysophospholipase from Pyrococcus abyssi - Arshia Nazir; Mohsin Shad; Hafiz Muzzammel Rehman; Naseema Azim; Muhammad Sajjad (World Journal of Microbiology and Biotechnology, 2024)

A control rod worth prediction using Adaptive Neuro-Fuzzy Inference System for Pre-Calibration Method at TRIGA PUSPATI Reactor - Teh Zhi Hui; Nur Syazwani Mohd Ali; Mohd Sabri Minhat; Jasman Zainal; Muhammad Arif Sazali; Muhammad Syahir Sarkawi; Khairulnadzmi Jamaluddin; Nor Afifah Basri; Mohsin Mohd Sies; Nahrul Khair Alang Md Rashid (Annals of Nuclear Energy, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

IoT-based agriculture management techniques for sustainable farming: A comprehensive review - Hammad Shahab; Muhammad Iqbal; Ahmed Sohaib; Farid Ullah Khan; Mohsin Waqas (Computers and Electronics in Agriculture, 2024)

Cadmium induced defense enhance the invasive potential of Wedelia trilobata under herbivore infestation - Mohsin Nawaz; Jianfan Sun; Yanwen Bo; Feng He; Samina Shabbir; Muhammad Umair Hassan; Linxuan Pan; Parvaiz Ahmad; Christian Sonne; Daolin Du (Journal of Hazardous Materials, 2024)

Downscaled GRACE/GRACE-FO observations for spatial and temporal monitoring of groundwater storage variations at the local scale using machine learning - Shoaib Ali; Jiangjun Ran; Behnam Khorrami; Haotian Wu; Aqil Tariq; Muhammad Jehanzaib; Muhammad Mohsin Khan; Muhammad Faisal (Groundwater for Sustainable Development, 2024)

Occurrence of diverse plant growth promoting bacteria in soybean [Glycine max (L.) Merrill] root nodules and their prospective role in enhancing crop yield - Mohsin Tariq; Nimra Tahreem; Marriam Zafar; Ghulam Raza; Muhammad Shahid; Muhammad Zunair; Wajeeha Iram; Syeda Tahseen Zahra (Biocatalysis and Agricultural Biotechnology, 2024)

Cryosphere: a frozen home of microbes and a potential source for drug discovery - Sahib Zada; Mohsin Khan; Zheng Su; Wasim Sajjad; Muhammad Rafiq (Archives of Microbiology, 2024)

Pathways to ecological resilience: exploring green energy and finance for sustainable development - Iqra Mehroush; Wasim Abbas Shaheen; Mohsin Shabir; Muhammad Talha (Environment, Development and Sustainability, 2024)

Unlocking Triticum aestivum L. resilience: Exogenous proline's remarkable role in mitigating lead stress, and delving into the secrets of TaGSK1 gene expression - Sidra Balooch; Sibgha Noreen; Seema Mahmood; Nida Zahra; Ahmad Azeem; Muhammad Mohsin Altaf; Muhammad Salim Akhter; Adeel Abbas (South African Journal of Botany, 2024)

Distribution characteristics of antibiotic resistance genes and microbial diversity in the inshore aquaculture area of Wenchang, Hainan, China - Yongqiang Qin; Xiaoyu Ren; Yankun Zhang; Hanye Ju; Jin Liu; Jia Xie; Muhammad Mohsin Altaf; Xiaoping Diao (Science of The Total Environment, 2024)

Reduced graphene oxide supported polyaniline/copper (II) oxide nanostructures for enhanced photocatalytic degradation of Congo red and hydrogen production from water - Mohsin Raza Dustgeer; Asim Jilani; Mohammad Omaish Ansari; Muhammad Bilal Shakoor; Shafaqat Ali; Aniqa Imtiaz; Hazirah Syahirah Zakria; Mohd Hafiz Dzarfan Othman (Journal of Water Process Engineering, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Scorpion sting in Hafizabad, Pakistan: Facility based epidemiological study - Muhammad Mohsin Ahsan; Zoya Gulzar; Hafiz Muhammad Tahir; Aamir Ali; Muhammad Ismail; Muhammad Khalid Mukhtar; Zain Ul Abdin (Toxicon, 2024)

Efficient synergistic degradation of Congo red and omeprazole in wastewater using rGO/Ag@ZnO nanocomposite - Nazish Kousar; Sufian Rasheed; Kousar Yasmeen; Abdul Rehman Umar; Mouna Hind Laiche; Mohsin Masood; Haji Muhammad; Muddasir Hanif (Journal of Water Process Engineering, 2024)

Land cover changes and carbon dynamics in Central India's dry tropical forests: A 25-year assessment and nature-based eco-restoration approaches - Tarun Kumar Thakur; S.L. Swamy; Anita Thakur; Alka Mishra; Sanjeev Bakshi; Amit Kumar; Muhammad Mohsin Altaf; Rupesh Kumar (Journal of Environmental Management, 2024)

Season shapes the functional diversity of microbial carbon metabolism in mangrove soils of Hainan Island, China - Haihua Wang; Huaiyang Ke; Hongping Wu; Siyuan Ma; Muhammad Mohsin Altaf; Xiaoping Diao (CATENA, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Sustainable yarns and fabrics from tri-blends of banana, cotton and tencel fibres for textile applications - Aamer Khan; Muhammad Awais; Muhammad Mohsin; Ayesha Khan; Kaleem Cheema (Journal of Cleaner Production, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

ZnO nanoparticles mediated by Azadirachta indica as nano fertilizer: Improvement in physiological and biochemical indices of Zea mays grown in Cr-contaminated soil - Sajid Mehmood; Wenjie Ou; Waqas Ahmed; Jochen Bundschuh; Muhammad Rizwan; Mohsin Mahmood; Haider Sultan; Juha M. Alatalo; Ahmed S.M. Elnahal; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

Development of a new hybrid ensemble method for accurate characterization of future drought using multiple global climate models - Mahrukh Yousaf; Zulfiqar Ali; Muhammad Mohsin; Maryam Ilyas; Muhammad Shakeel (Stochastic Environmental Research and Risk Assessment, 2023)

Engineering of Chlamydomonas reinhardtii chloroplast for mucosal immunotherapeutic against Newcastle disease virus - Sania Naeem; Naila Shahid; Mohsin Ahmad Khan; Saira Azam; Muhammad Saad Bhutta; Ayesha Latif; Aneela Yasmeen; Tahir Rehman Sami Ullah; Abdul Qayyum Rao; Kausar Malik (Journal of Applied Phycology, 2023)

Probabilistic modelling of interarrival time of drought for different operational drought indices used in Pakistan - Muhammad Mohsin; Shahzada Adnan (International Journal of Climatology, 2023)
Adverse climate changes in Pakistan undermine the water resources and give rise to transient and permanent droughts in different parts of the country. The occurrence of drought cannot be prevented, but its detrimental impacts can be brought down by proper pre‐drought planning. Effective planning owes to using scientific and probabilistic approaches. In this paper, the interarrival time of drought for seven operational drought indices in Pakistan is modelled by using the modified distribution of convolution derived from the Bivariate Affine Linear Exponential (BALE) distribution. A new stochastic variable, interarrival time of drought, is generated from the data of drought indices from 1951 to 2016 used in Pakistan by applying the theory of runs. The proposed model identifies Palmer drought severity index (PDSI) and Reconnaissance drought index (RDI) as the most appropriate meteorological indices for the under‐study country. The quantiles of the model are computed that provide information about the interarrival time of drought and help to anticipate this phenomenon. In addition, return periods for all the seven indices are calculated to report the frequency and duration of drought over a certain period. Finally, some recommendations for the National Drought Monitoring Centre (NDMC) and Pakistan Council of Research in Water Resources (PCRWR) are stated for better future planning to avoid the adverse impacts of drought.

Deep-Neural-Network-Based Receiver Design for Downlink Non-Orthogonal Multiple-Access Underwater Acoustic Communication - Habib Hussain Zuberi; Songzuo Liu; Muhammad Bilal; Ayman Alharbi; Amar Jaffar; Syed Agha Hussnain Mohsan; Abdulaziz Miyajan; Mohsin Abrar Khan (Journal of Marine Science and Engineering, 2023)
The excavation of the ocean has led to the submersion of numerous autonomous vehicles and sensors. Hence, there is a growing need for multi-user underwater acoustic communication. On the other hand, due to the limited bandwidth of the underwater acoustic channel, downlink non-orthogonal multiple access (NOMA) is one of the fundamental pieces of technology for solving the problem of limited bandwidth, and it is expected to be beneficial for many modern wireless underwater acoustic applications. NOMA downlink underwater acoustic communication (UWA) is accomplished by broadcasting data symbols from a source station to several users, which uses superimposed coding with variable power levels to enable detection through successive interference cancellation (SIC) receivers. Nevertheless, comprehensive information of the channel condition and channel state information (CSI) are both essential for SIC receivers, but they can be difficult to obtain, particularly in an underwater environment. To address this critical issue, this research proposes downlink underwater acoustic communication using a deep neural network utilizing a 1D convolution neural network (CNN). Two cases are considered for the proposed system in the first case: in the first case, two users with different power levels and distances from the transmitter employ BPSK and QPSK modulations to support multi-user communication, while, in the second case, three users employ BPSK modulation. Users far from the base station receive the most power. The base station uses superimposed coding. The BELLHOP ray-tracing algorithm is utilized to generate the training dataset with user depth and range modifications. For training the model, a composite signal passes through the samples of the UWA channel and is fed to the model along with labels. The DNN receiver learns the characteristic of the UWA channel and does not depend on CSI. The testing CIR is used to evaluate the trained model. The results are compared to the traditional SIC receiver. The DNN-based DL NOMA underwater acoustic receiver outperformed the SIC receiver in terms of BER in simulation results for all the modulation orders.

Evaluation of sustainable development of the Bohai Sea Rim based on integrated land–sea management: a multi-system coupling and coordination study at coastal, provincial, and city level - Jinling Yan; Yongjie Xue; Huilan Wu; Dahai Li; Muhammad Mohsin (Frontiers in Marine Science, 2023)
Based on the Integrated Land–Sea Management, this study established a theoretical framework for the sustainability of coastal regions by combining sustainable development with coupling coordination theory. The improved coupling coordination model was used to analyze the sustainable development of the Bohai Rim and its coastal provinces and cities from 2006 to 2020. Our implications were as follows: (1) The theoretical framework showed an S -shaped spiral trend, and the empirical results on the Bohai Rim were consistent with the trajectory conclusions. (2) The economic subsystem played a crucial role in the system’s evolution toward sustainable development. (3) The region and city models demonstrated consistent coupling and coordination development degrees. However, the consistency was not completely synchronous. Conscious eco-environmental governance activities can promote benign interactions among systems and improve this relationship. (4) The sustainable development of coastal cities is different from that of the provinces in which they are located. It merely demonstrates their relative status among all coastal cities and does not fully represent the wider region in which they are located. The findings suggest that adaptive policies, whether economic, social or environmental, can promote sustainable development. Economic stimulus policies can promote a transition of sustainable development; in the economic downturn, the adaptive environmental policy is realized by adjusting the relationship between subsystems to promote the coordination of regional systems, preparing for the next sustainable system transition. The established theoretical model and improvised mathematical method can be extended to study various coastal regions

Corrigendum to “Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data” - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh; et al. (Groundwater for Sustainable Development, 2023)

Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh (Groundwater for Sustainable Development, 2023)

Unfolding impact of natural resources, economic growth, and energy nexus on the sustainable environment: Guidelines for green finance goals in 10 Asian countries - Muhammad Mohsin; Fouad Jamaani (Resources Policy, 2023)

A novel deep-learning technique for forecasting oil price volatility using historical prices of five precious metals in context of green financing – A comparison of deep learning, machine learning, and statistical models - Muhammad Mohsin; Fouad Jamaani (Resources Policy, 2023)

Assessment of application of ZnO nanoparticles on physiological profile, root architecture and antioxidant potential of Solanum lycopersicum - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Nida Zainab; Naeem Ali; Muhammad Farooq Hussain Munis; Muhammad Iftikhar; Hassan Javed Chaudhary (Biocatalysis and Agricultural Biotechnology, 2023)

A generalized procedure for joint monitoring and probabilistic quantification of extreme climate events at regional level - Aamina Batool; Zulfiqar Ali; Muhammad Mohsin; Muhammad Shakeel (Environmental Monitoring and Assessment, 2023)

RETRACTED ARTICLE: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2023)

Estimating Photosynthetically Active Euphotic Layer in Major Lakes of Kumaun Region Using Secchi Depth - Zainab Khan; Sk Ajim Ali; Mohammad Mohsin; Syed Kausar Shamim; Ekaterina Mankovskaya; Farhana Parvin; Nikhat Bano; Ateeque Ahmad; Muhammad Yousuf Jat Baloch (Water, Air, & Soil Pollution, 2023)

A Common Factor Analysis Based Data Mining Procedure for Effective Assessment of 21st Century Drought under Multiple Global Climate Models - Muhammad Ahmad; Zulfiqar Ali; Maryam Ilyas; Muhammad Mohsin; Rizwan Niaz (Water Resources Management, 2023)

The Dynamics of the Relationship Between Water Availability, Water Equity, Economic Benefits and Water User Associations’ Performance: A PLS-SEM Approach - Mohsin Riaz; Muhammad Ashfaq; Ismet Boz; Pomi Shahbaz (Water Resources Management, 2023)

Feed intake, feeding behavior, growth performance, nutrient digestibility, and carcass characteristics of goats fed pelleted total mixed rations with varying Rhodes hay levels - Muhammad Irfan Malik; Xuezhao Sun; Muhammad Afzal Rashid; Muhammad Amer Sohail; Muhammad Shahbaz Yousaf; Habib Ur Rehman; Imran Mohsin; Jianping Li (Small Ruminant Research, 2023)

Green finance and the socio-politico-economic factors’ impact on the future oil prices: Evidence from machine learning - Muhammad Mohsin; Fouad Jamaani (Resources Policy, 2023)

Effects of Saccharomyces cerevisiae live cells and culture on growth and productive performance in lactating Nili-Ravi buffaloes - Mohsin Ali; Saeed Ahmed; Mubashar Ali; Nisar Ahmad; Mohammad Noman Tariq; Muhammad Usman; Ahmad Azeem Sardar (Tropical Animal Health and Production, 2023)

Phytohormones Mediated Modulation of Abiotic Stress Tolerance and Potential Crosstalk in Horticultural Crops - Muhammad Ahsan Altaf; Rabia Shahid; Ravinder Kumar; Muhammad Mohsin Altaf; Awadhesh Kumar; Latif Ullah Khan; Muhammad Saqib; Muhammad Azher Nawaz; Bushra Saddiq; Saraj Bahadur; Rahul Kumar Tiwari; Milan Kumar Lal; et al. (Journal of Plant Growth Regulation, 2023)

RETRACTED ARTICLE: Melatonin-Polyamine Interplay in the Regulation of Stress Responses in Plants - Rahul Kumar Tiwari; Ravinder Kumar; Milan Kumar Lal; Awadhesh Kumar; Muhammad Ahsan Altaf; Rajni Devi; Vikas Mangal; Safina Naz; Muhammad Mohsin Altaf; Abhijit Dey; Tariq Aftab (Journal of Plant Growth Regulation, 2023)

Microbial biochemical pathways of arsenic biotransformation and their application for bioremediation - Hareem Mohsin; Maria Shafique; Muhammad Zaid; Yasir Rehman (Folia Microbiologica, 2023)

A systematic review on the bioremediation of metal contaminated soils using biochar and slag: current status and future outlook - Sajid Mehmood; Waqas Ahmed; Juha M. Alatalo; Mohsin Mahmood; Rana Muhammad Ammar Asghar; Muhammad Imtiaz; Naseer Ullah; Wei-dong Li; Allah Ditta (Environmental Monitoring and Assessment, 2023)

Does green investments improve air quality? Evidence for developed and developing European countries - Metin İlbasmış; Mücahit Çitil; Furkan Demirtaş; Muhammad Ali; Abdulkadir Barut; Mohammad Mohsin (Environmental Science and Pollution Research, 2023)

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Unearthing research trends in emissions and sustainable development: Potential implications for future directions - Khalid Mehmood; Saifullah; Xuchun Qiu; Muhammad Mohsin Abrar (Gondwana Research, 2023)

Synthesis, characterization and antifungal potential of titanium dioxide nanoparticles against fungal disease (Ustilago tritici) of wheat (Triticum aestivum L.) - Nadiyah M. Alabdallah; Muhammad Atif Irshad; Muhammad Rizwan; Rab Nawaz; Aqil Inam; Muhammad Mohsin; Iram Khurshid; Hesham F. Alharby; Atif A. Bamagoos; Shafaqat Ali (Environmental Research, 2023)

Bio-fabrication of zinc oxide nanoparticles from Picea smithiana and their potential antimicrobial activities against Xanthomonas campestris pv. Vesicatoria and Ralstonia solanacearum causing bacterial leaf spot and bacterial wilt in tomato - Fazal ur Rehman; Najeeba Paree Paker; Mohsin Khan; Muhammad Naeem; Muhammad Farooq Hussain Munis; Shafiq ur Rehman; Hassan Javed Chaudhary (World Journal of Microbiology and Biotechnology, 2023)

RETRACTED: Source, occurrence, distribution, fate, and implications of microplastic pollutants in freshwater on environment: A critical review and way forward - Tonni Agustiono Kurniawan; Ahtisham Haider; Hafiz Muhammad Ahmad; Ayesha Mohyuddin; Hafiz Muhammad Umer Aslam; Sohail Nadeem; Mohsin Javed; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Kit Wayne Chew (Chemosphere, 2023)

Aquaculture sediments amended with biochar improved soil health and plant growth in a degraded soil - Sajid Mehmood; Waqas Ahmed; Mohsin Mahmood; Muhammad Shahid Rizwan; Rana Muhammad Ammar Asghar; Juha M. Alatalo; Muhammad Imtiaz; Muhammad Akmal; Hamada Abdelrahman; Jifu Ma; Esmat F. Ali; Weidong Li; et al. (Marine Pollution Bulletin, 2023)

Using econometric and machine learning models to forecast crude oil prices: Insights from economic history - Zilin Xu; Muhammad Mohsin; Kaleem Ullah; Xiaoyu Ma (Resources Policy, 2023)

Adsorption of Pb(II) from wastewater using a red mud modified rice-straw biochar: Influencing factors and reusability - Waqas Ahmed; Sajid Mehmood; Mohsin Mahmood; Sehrish Ali; Awais Shakoor; Avelino Núñez-Delgado; Rana Muhammad Ammar Asghar; Hongwei Zhao; Wenjie Liu; Weidong Li (Environmental Pollution, 2023)

Replacing ground Rhodes grass hay with soyhulls in the pelleted diet: effects on ingestive behavior, nutrient digestibility, blood metabolites, growth performance, and economic viability of intensive fattening Lohi lambs - Muhammad Khan; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Imran Mohsin; Habib Ur Rehman (Tropical Animal Health and Production, 2023)

Role of artificial intelligence on green economic development: Joint determinates of natural resources and green total factor productivity - Lei Chang; Farhad Taghizadeh-Hesary; Muhammad Mohsin (Resources Policy, 2023)

Impact of seasonal variations on incidence and laterality of testicular torsion - Ronen Rub; Ghalib Lidawi; Ekaterina Laukhtina; Mohsin Asali; Muhammad Majdoub (International Journal of Biometeorology, 2023)

Effects of prepartum melatonin treatment and suckling on postpartum reproductive performance of Beetal goats under subtropical conditions - Muhammad Afzaal; Muhammad Irfan-ur-Rehman Khan; Waqas Ahmad; Amir Hayat; Qasir Abbas; Muhammad Arshad; Nasir Hameed; Imran Mohsin; Amjad Riaz (Small Ruminant Research, 2023)

Cadmium accumulation by Phragmites australis and Iris pseudacorus from stormwater in floating treatment wetlands microcosms: Insights into plant tolerance and utility for phytoremediation - Muhammad Mohsin; Nicole Nawrot; Ewa Wojciechowska; Suvi Kuittinen; Katarzyna Szczepańska; Grażyna Dembska; Ari Pappinen (Journal of Environmental Management, 2023)

Moringa oleifera leaf extract mediated green synthesis of silver nanoparticles and their antibacterial effect against selected gram-negative strains - Mehwish Younas; Muhammad Hidayat Rasool; Mohsin Khurshid; Amjad Khan; Muhammad Zeshan Nawaz; Ijaz Ahmad; Muhammad Nazim Lakhan (Biochemical Systematics and Ecology, 2023)

Impact of eco-friendly chemical pretreatment on physicochemical and surface mechanical properties of sustainable lignocellulosic agricultural waste - Muhammad Sulaiman; Fahad Ali Rabbani; Tanveer Iqbal; Mohsin Ali Kazmi; Saima Yasin; M.A. Mujtaba; M.A. Kalam; Fares Almomani (Algal Research, 2023)

Does hydropower energy help to reduce CO2 emissions in European Union countries? evidence from quantile estimation - Muhammad Mohsin; Darkhan Orynbassarov; Muhammad Khalid Anser; Yessengali Oskenbayev (Environmental Development, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

A review of particulate pollution over Himalaya region: Characteristics and salient factors contributing ambient PM pollution - Muhammad Azher Hassan; Tariq Mehmood; Junjie Liu; Xiaosan Luo; Xinghua Li; Mohsin Tanveer; Muhammad Faheem; Awais Shakoor; Afzal Ahmed Dar; Muhammad Abid (Atmospheric Environment, 2023)

Individual and Synergic Effects of Phosphorus and Gibberellic Acid on Organic Acids Exudation Pattern, Ultra-Structure of Chloroplast and Stress Response Gene Expression in Cu-Stressed Jute (Corchorus Capsularis L.) - Aishah Alatawi; Xiukang Wang; Muhammad Hamzah Saleem; Muhammad Mohsin; Muzammal Rehman; Kamal Usman; Shah Fahad; Manar Fawzi Bani Mfarrej; Daniel Ingo Hefft; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Factorial analysis for the impact on filtration properties of water-based drilling fluid after the addition of graphene oxide, pure-bore, and sodium alginate - Shaine Mohammadali Lalji; Syed Imran Ali; Muhammad Mohsin Yousufi; Muhammad Arsalan Sultan; Khizra Fatima; Abdur Rahman Misbah (Arabian Journal of Geosciences, 2023)

Efficacy of marigold (Tagetes erecta L.) for the treatment of tannery and surgical industry wastewater under citric acid amendment: a lab scale study - Arooj Fatima; Mujahid Farid; Zaki Ul Zaman Asam; Muhammad Zubair; Sheharyaar Farid; Mohsin Abbas; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Assessing green financing with emission reduction and green economic recovery in emerging economies - Miaonan Lin; Haorong Zeng; Xin Zeng; Muhammad Mohsin; Syed Mubashar Raza (Environmental Science and Pollution Research, 2023)

Polygenic and autosomally inherited dimethoate resistance in Amrasca biguttula biguttula with no cross-resistance to bifenthrin, imidacloprid, and chlorfenapyr - Iqra Khalid; Muhammad Mohsin; Muhammad Abubakar; Sarfraz Ali Shad; Muhammad Binyameen (Crop Protection, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Application of Nanomaterials for Cadmium Adsorption for Sustainable Treatment of Wastewater: a Review - Muhammad Atif Irshad; Rab Nawaz; Ewa Wojciechowska; Muhammad Mohsin; Nicole Nawrot; Iqra Nasim; Fida Hussain (Water, Air, & Soil Pollution, 2023)

Nickel toxicity pretreatment attenuates salt stress by activating antioxidative system and ion homeostasis in tomato (Solanum lycopersicon L.): an interplay from mild to severe stress - Muhammad Azeem Subhani; Muhammad Amjad; Muhammad Mohsin Iqbal; Behzad Murtaza; Muhammad Imran; Muhammad Asif Naeem; Ghulam Abbas; Mathias Neumann Andersen (Environmental Geochemistry and Health, 2023)

Correction to: Role of climate fund raising under fiscal balance on climate change mitigation: an analysis from Pareto optimality - Jie Ding; Ying Wang; Siqi Wang; Muhammad Mohsin (Environmental Science and Pollution Research, 2022)

Protective Mechanisms of Melatonin Against Vanadium Phytotoxicity in Tomato Seedlings: Insights into Nutritional Status, Photosynthesis, Root Architecture System, and Antioxidant Machinery - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Latif Ullah Khan; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Muhammad Azher Nawaz; Safina Naz; Sidra Shahid; Milan Kumar Lal; Rahul Kumar Tiwari; Muhammad Adnan Shahid (Journal of Plant Growth Regulation, 2022)

A multi-criteria approach to investigate spatial distribution, sources, and the potential toxicological effect of polycyclic aromatic hydrocarbons (PAHs) in sediments of urban retention tanks - Nicole Nawrot; Anna Pouch; Karolina Matej-Łukowicz; Ksenia Pazdro; Muhammad Mohsin; Shahabaldin Rezania; Ewa Wojciechowska (Environmental Science and Pollution Research, 2022)
Bottom sediments deposited in retention tanks (RTs) located on two urban streams (Oliwski and Strzyza) in the central part of Gdansk (Poland) were analysed for polycyclic aromatic hydrocarbons’ (PAHs) content. PAHs were extracted from samples with methylene chloride, then the extracts were subjected to clean-up applying the solid phase extraction (SPE) method. Quantitative and qualitative determination of 16 PAHs was performed with the use of gas chromatography/mass spectrometry technique. A multi-dimensional approach was applied to analyse PAHs’ spatial distribution, source, and contamination status. Potential sources of PAHs were verified using isomer ratios supported by a statistical approach. The Σ16PAHs (in mg/kg d.w.) ranged from 1.95 ± 0.64 to 20.4 ± 6.8 for RTs located on the Oliwski Stream and from 0.50 ± 0.17 to 8.6 ± 2.9 for RTs located on the Strzyza Stream. PAHs detected in bottom sediments were mainly composed of 4- and 5-ring compounds. PAH isomer ratios such as Phen/Anth, Flth/Pyr, B(a)A/B(a)A + Chry, Inpy/Inpy + B(ghi)P, Flth/Flth + Pyr, Anth/Anth + Phen, and Flth/Flth + Pyr suggested delivery pathways for biomass, coal, and petroleum combustion. Petrogenic PAHs related to fuel leaks from cars were not detected. Statistical analyses confirmed traffic and heating system sources, while factor analysis (FA) pointed out the abrasion of wasting parts of vehicles. Based on threshold levels presented in sediment quality guidelines (SQGs), in most cases, PAHs were at low levels with occasional negative biological effects on organisms. Only sediments deposited in two RTs located on the Oliwski Stream presented harmful features for sediment-dwelling organisms. The risk assessment performed accordingly to the Σ16PAHs presented a moderate and high risk for biota. This study not only reflects the direct threat related to PAH content in bottom sediments, but also highlights the overall pollution of an area, considered to be a recreational part of the city (Oliwski Stream catchment). The findings of this study highlight the need to launch preventative methods to protect the area against pollution from heating system emission and traffic.

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Assessing the nexus between COVID-19 pandemic–driven economic crisis and economic policy: lesson learned and challenges - Lei Chang; Muhammad Mohsin; Wasim Iqbal (Environmental Science and Pollution Research, 2022)

Damage assessment of stored grain pests against rice grains types and wheat - Muhammad Waqar Hassan; Mohsin Ali Hashmi; Ghulam Sarwar; Zahid Mehmood; Warda Saleem; Muhammad Aslam Farooqi (International Journal of Tropical Insect Science, 2022)

RETRACTED ARTICLE: Role of climate fund raising under fiscal balance on climate change mitigation: an analysis from Pareto optimality - Jie Ding; Ying Wang; Siqi Wang; Muhammad Mohsin (Environmental Science and Pollution Research, 2022)

Linking Plants Functioning to Adaptive Responses Under Heat Stress Conditions: A Mechanistic Review - Mahmood Ul Hassan; Tassaduq Rasool; Chandni Iqbal; Adnan Arshad; Muhammad Abrar; Muhammad Mohsin Abrar; Muhammad Habib-ur-Rahman; Mehmood Ali Noor; Alam Sher; Shah Fahad (Journal of Plant Growth Regulation, 2022)

Renewable energy, industrial upgradation, and import-export quality: green finance and CO2 emission reduction nexus - Lu Lu; Zhen Liu; Muhammad Mohsin; Chunlian Zhang (Environmental Science and Pollution Research, 2022)

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

Assessing Salt Tolerance Induction in Potato by Salicylic Acid Using Morpho-Physio-Biochemical, Ionic, and Yield Indices - Hafiz Nazar Faried; C. M. Ayyub; Fahad Masoud Wattoo; Mohsin Bashir; Kashif Razzaq; Gulzar Akhtar; Abid Hussain; Sami Ullah; Javed Iqbal Wattoo; Muhammad Amin; Shoaib Munir; Muhammad Rashid Shaheen; et al. (Potato Research, 2022)

CRISPR-Cas9 based stress tolerance: New hope for abiotic stress tolerance in chickpea (Cicer arietinum) - Muhammad Khuram Razzaq; Muhammad Akhter; Ramala Masood Ahmad; Kaiser Latif Cheema; Aiman Hina; Benjamin Karikari; Ghulam Raza; Guangnan Xing; Junyi Gai; Mohsin Khurshid (Molecular Biology Reports, 2022)

Structural and Electronic (Absorption and Fluorescence) Properties of a Stable Triplet Diphenylcarbene: A DFT Study - Abrar Ul Hassan; Ayesha Mohyuddin; Sohail Nadeem; Cihat Güleryüz; Sadaf Ul Hassan; Mohsin Javed; Muhammad Salman Muhsan (Journal of Fluorescence, 2022)

Heavy metal pollution in the soil of a riverine basin: distribution, source, and potential hazards - Kifayatullah Khan; Abdul Mohsin; Hafiz Muhammad Adeel Sharif; Afsheen Maryam; Jafar Ali; Xu Li; Sobhy Mostafa Ibrahim; Muhammad Ayaz; Yunqiao Zhou; Muhammad Younas (Environmental Monitoring and Assessment, 2022)

Correction to: Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Pathological effects of graded doses of aflatoxin B1 on the development of the testes in juvenile white leghorn males - Anas Ashraf; Muhammad Kashif Saleemi; Mashkoor Mohsin; Shafia Tehseen Gul; Muhammad Zubair; Faqir Muhammad; Sheraz Ahmed Bhatti; Muhammad Raza Hameed; Muhammad Imran; Hamid Irshad; Iqra Zaheer; Ishtiaq Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Does energy use and economic growth allow for environmental sustainability? An empirical analysis of Pakistan - Muhammad Mohsin; Sobia Naseem; Muddassar Sarfraz; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

Examining the Effects of Normal Ageing on Cortical Connectivity of Older Adults - Muhammad Aamir Panhwar; Muhammad Mohsin Pathan; Nasrullah Pirzada; Muhammad Aashed Khan Abbasi; Deng ZhongLiang; Ghazala Panhwar (Brain Topography, 2022)

Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Salicylic Acid Induces Vanadium Stress Tolerance in Rice by Regulating the AsA-GSH Cycle and Glyoxalase System - Muhammad Mohsin Altaf; Xiao-ping Diao; Haihua Wang; Latif Ullah Khan; Atique ur Rehman; Awais Shakoor; Muhammad Ahsan Altaf; Taimoor Hassan Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Gums-based engineered bio-nanostructures for greening the 21st-century biotechnological settings - Muhammad Bilal; Hira Munir; Muhammad Imran Khan; Mohsin Khurshid; Tahir Rasheed; Komal Rizwan; Marcelo Franco; Hafiz M. N. Iqbal (Critical Reviews in Food Science and Nutrition, 2022)

Biochar increases salt tolerance and grain yield of quinoa on saline-sodic soil: multivariate comparison of physiological and oxidative stress attributes - Ghulam Abbas; Muhammad Mohsin Abrar; Muhammad Asif Naeem; Manzer H. Siddiqui; Hayssam M. Ali; Yantao Li; Khalil Ahmed; Nan Sun; Minggang Xu (Journal of Soils and Sediments, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Evaluation of the community participation in solid waste management: case of the city of Bulawayo, Zimbabwe - Joseph Mutemani; Annatoria Chinyama; Muhammad Mohsin; Tendai Kativhu (Arabian Journal of Geosciences, 2022)

Effects of replacement of wheat straw with corn stover-based TMR on growth performance, behavioral characteristics, selected blood metabolites, and nutrient digestibility in Beetal bucks - Faisal Majeed; Saeed Ahmed; Muhammad Afzal Rashid; Muhammad Qamar Shahid; Imran Mohsin (Tropical Animal Health and Production, 2022)

A blessing in disguise: new insights on the effect of COVID-19 on the carbon emission, climate change, and sustainable environment - Muddassar Sarfraz; Muhammad Mohsin; Sobia Naseem (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2022)

Melatonin Mitigates Cadmium Toxicity by Promoting Root Architecture and Mineral Homeostasis of Tomato Genotypes - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Safina Naz; Muhammad Mohsin Altaf; Latif Ullah Khan; Milan Kumar Lal; Rahul Kumar Tiwari; Awais Shakoor (Journal of Soil Science and Plant Nutrition, 2022)

Delineating Vanadium (V) Ecological Distribution, Its Toxicant Potential, and Effective Remediation Strategies from Contaminated Soils - Muhammad Mohsin Altaf; Xiao-ping Diao; Awais Shakoor; Muhammad Imtiaz; Atique-ur-Rehman; Muhammad Ahsan Altaf; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2022)

Physiological impacts on construction workers under extremely hot and humid weather - Ammar Moohialdin; Bambang Trigunarsyah; Muhammad Saiful Islam; Mohsin K. Siddiqui (International Archives of Occupational and Environmental Health, 2022)

Financial impact of energy efficiency and energy policies aimed at power sector reforms: mediating role of financing in the power sector - Hongda Liu; Abdul Razzaq Khan; Sumaira Aslam; Abdul Khaliq Rasheed; Muhammad Mohsin (Environmental Science and Pollution Research, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Green energy security assessment in Morocco: green finance as a step toward sustainable energy transition - Fatima Zahra Ainou; Mohsin Ali; Muhammad Sadiq (Environmental Science and Pollution Research, 2022)

The influence of energy consumption and economic growth on environmental degradation in BRICS countries: an application of the ARDL model and decoupling index - Sobia Naseem; Muhammad Mohsin; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muddassar Sarfraz (Environmental Science and Pollution Research, 2022)

Transporters and transcription factors gene families involved in improving nitrogen use efficiency (NUE) and assimilation in rice (Oryza sativa L.) - Tahmina Nazish; Mamoona Arshad; Sami Ullah Jan; Ayesha Javaid; Muhammad Hassaan Khan; Muhammad Afzal Naeem; Muhammad Baber; Mohsin Ali (Transgenic Research, 2022)

Biofertilizer microorganisms accompanying pathogenic attributes: a potential threat - Mohsin Tariq; Farwah Jameel; Usman Ijaz; Muhammad Abdullah; Kamran Rashid (Physiology and Molecular Biology of Plants, 2022)

Multidimensional perspective of green financial innovation between green intellectual capital on sustainable business: the case of Pakistan - Hafeez Ullah; Zhuquan Wang; Muhammad Mohsin; Weiying Jiang; Hasnain Abbas (Environmental Science and Pollution Research, 2022)

Assessment of sustainability and uncertainties of oil markets: mediating determinants of energy use and CO2 emissions - Muhammad Mohsin; Shahid Bashir; Zulfiqar Ali Baloch; Mohammad Hafeez (Environmental Science and Pollution Research, 2022)

Phenomena, factors of wax deposition and its management strategies - Syed Imran Ali; Shaine Mohammadali Lalji; Javed Haneef; Muhammad Arqam Khan; Mohsin Yousufi; Nimra Yousaf; Abdus Saboor (Arabian Journal of Geosciences, 2022)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

Assessing the capacity of renewable power production for green energy system: a way forward towards zero carbon electrification - FengSheng Chien; Quang-Thanh Ngo; Ching-Chi Hsu; Ka Yin Chau; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

Modeling the relationship between carbon emissions and environmental sustainability during COVID-19: a new evidence from asymmetric ARDL cointegration approach - Muddassar Sarfraz; Muhammad Mohsin; Sobia Naseem; Amit Kumar (Environment, Development and Sustainability, 2021)

Genomic features of a high-risk mcr-1.1-positive Escherichia coli ST10 isolated from cattle farm environment - Arslan Ali; Herrison Fontana; Elder Sano; Ruichao Li; Muhammad Humayon; Sadeequr Rahman; Nilton Lincopan; Mashkoor Mohsin (Environmental Science and Pollution Research, 2021)

How energy insecurity leads to energy poverty? Do environmental consideration and climate change concerns matters - Syed Ehsanullah; Quyen Ha Tran; Muhammad Sadiq; Shahid Bashir; Muhammad Mohsin; Robina Iram (Environmental Science and Pollution Research, 2021)

Evaluating green innovation and performance of financial development: mediating concerns of environmental regulation - Ching-Chi Hsu; Ngo Quang-Thanh; FengSheng Chien; Li Li; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

Melatonin Mitigates Nickel Toxicity by Improving Nutrient Uptake Fluxes, Root Architecture System, Photosynthesis, and Antioxidant Potential in Tomato Seedling - Muhammad Ahsan Altaf; Rabia Shahid; Ming-Xun Ren; Muhammad Mohsin Altaf; Mohammad Shah Jahan; Latif Ullah Khan (Journal of Soil Science and Plant Nutrition, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Climatological and social fallacies about COVID-19 pandemic - Ambar Farooq; Uttam Kumar; Junaite Bin Gais Uddin; Muhammad Haroon U. Rashid; Matoor Mohsin Gilani; Taimoor Hassan Farooq; Awais Shakoor; Matloob Ahmad (Environmental Sustainability, 2021)

Impact of green trust and green perceived quality on green purchase intentions: a moderation study - Allah Wasaya; Muhammad Abid Saleem; Jamil Ahmad; Muhammad Nazam; M. Mohsin Ali Khan; Mohammad Ishfaq (Environment, Development and Sustainability, 2021)

Origin, Pathogenesis, Diagnosis and Treatment Options for SARS-CoV-2: A Review - Humna Sajjad; Mohsin Majeed; Saiqa Imtiaz; Mariyam Siddiqah; Anila Sajjad; Misbahud Din; Muhammad Ali (Biologia, 2021)

Stochastic model for drought analysis of the Colorado River Basin - Muhammad Mohsin; Juergen Pilz (Stochastic Environmental Research and Risk Assessment, 2021)

Correction to: Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Long-term fertilization alters chemical composition and stability of aggregate-associated organic carbon in a Chinese red soil: evidence from aggregate fractionation, C mineralization, and 13C NMR analyses - Adnan Mustafa; Xu Hu; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Ali Akbar Maitlo; Kashif Ali Kubar; Qudsia Saeed; Muhammad Kamran; Muhammad Naveed; Wang Boren; Sun Nan; Xu Minggang (Journal of Soils and Sediments, 2021)

Assessing the socio-economic viability of solar commercialization and electrification in south Asian countries - Huaping Sun; Rehmat Ullah Awan; Muhammad Atif Nawaz; Muhammad Mohsin; Abdul Khaliq Rasheed; Nadeem Iqbal (Environment, Development and Sustainability, 2021)

Phytochemical profiling, in vitro and in vivo anti-inflammatory, analgesic and antipyretic potential of Sesuvium sesuvioides (Fenzl) Verdc. (Aizoaceae) - M. Sajid-ur-Rehman; Saiqa Ishtiaq; Mohsin Abbas Khan; Meshal Alshamrani; Muhammad Younus; Ghazala Shaheen; Muhammad Abdullah; Ghulam Sarwar; Muhammad Sohaib Khan; Faraza Javed (Inflammopharmacology, 2021)

Mechanism and role of seeded native grasses to immobilize nitrogen on harvested blanket peat forests for protection of water courses - Zaki-ul-Zaman Asam; Connie O’Driscoll; Mohsin Abbas; Mark O’Connor; Muhammad Waqas; Mohammad Rehan; Abdul-Sattar Nizami; Liwen Xiao (Environmental Science and Pollution Research, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Does tradeoff between financial and social indicators matters in environmental consideration: evidence from G7 region - Nguyen Van Song; Nguyen Thi Minh Phuong; Thai Thi Kim Oanh; Do Huy Chien; Vu Quang Phuc; Muhammad Mohsin (Environmental Science and Pollution Research, 2021)

Heat-related illnesses in a mass gathering event and the necessity for newer diagnostic criteria: a field study - Wesam Alkassas; Ahmad Mamoun Rajab; Sara T. Alrashood; Muhammad Ayub Khan; Mahmoud Dibas; Mohsin Zaman (Environmental Science and Pollution Research, 2021)

Influence of Nitrogen Fertilization Pattern on Productivity, Nitrogen Use Efficiencies, and Profitability in Different Rice Production Systems - Muhammad Ishfaq; Nadeem Akbar; Usman Zulfiqar; Nauman Ali; Khawar Jabran; Mohsin Nawaz; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Managerial policy and economic analysis of wind-generated renewable hydrogen for light-duty vehicles: Green solution of energy crises - Jingyi Liu; Qaiser Abbas; Majed Alharthi; Muhammad Mohsin; Farhat Rasul; Nadeem Iqbal (Environmental Science and Pollution Research, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

Research advances and applications of biosensing technology for the diagnosis of pathogens in sustainable agriculture - Qurban Ali; Sunny Ahmar; Muhammad Aamir Sohail; Muhammad Kamran; Mohsin Ali; Muhammad Hamzah Saleem; Muhammad Rizwan; Agha Mushtaque Ahmed; Freddy Mora-Poblete; Antônio Teixeira do Amaral Júnior; Mustansar Mubeen; Shafaqat Ali (Environmental Science and Pollution Research, 2021)

Assessing the perceived impact of exploration and production of hydrocarbons on households perspective of environmental regulation in Ghana - David Ajene Alemzero; Nadeem Iqbal; Sajid Iqbal; Muhammad Mohsin; Ngonadi Josiah Chukwuma; Burhan Ali Shah (Environmental Science and Pollution Research, 2021)

Assessing energy security in Africa based on multi-dimensional approach of principal composite analysis - David Ajene Alemzero; Huaping Sun; Muhammad Mohsin; Nadeem Iqbal; Muhammad Nadeem; Xuan Vinh Vo (Environmental Science and Pollution Research, 2021)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Effect of Vanadium on Growth, Photosynthesis, Reactive Oxygen Species, Antioxidant Enzymes, and Cell Death of Rice - Muhammad Mohsin Altaf; Xiao-ping Diao; Atique ur Rehman; Muhammad Imtiaz; Awais Shakoor; Muhammad Ahsan Altaf; Haseeb Younis; Pengcheng Fu; Muhammad Usman Ghani (Journal of Soil Science and Plant Nutrition, 2020)

Novel loss-of-function mutations in COCH cause autosomal recessive nonsyndromic hearing loss - Kevin T. Booth; Amama Ghaffar; Muhammad Rashid; Luke T. Hovey; Mureed Hussain; Kathy Frees; Erika M. Renkes; Carla J. Nishimura; Mohsin Shahzad; Richard J. Smith; Zubair Ahmed; Hela Azaiez; et al. (Human Genetics, 2020)

Correction to: Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Assessment of European and hybrid aspen clones efficiency based on height growth and removal percentage of petroleum hydrocarbons—a field trial - Mir Md Abdus Salam; Muhammad Mohsin; Fahad Rasheed; Muhammad Ramzan; Zikria Zafar; Pertti Pulkkinen (Environmental Science and Pollution Research, 2020)
Soils polluted by organic or inorganic pollutants are an emerging global environmental issue due to their toxic effects. A phytoremediation experiment was conducted to evaluate the extraction potential of three European aspen clones (R2, R3, and R4) and seven hybrid aspen clones (14, 27, 34, 134, 172, 191, and 291) grown in soils polluted with hydrocarbons (includes polycyclic aromatic hydrocarbons (PAH) and total petroleum hydrocarbons (TPH)). Height growth, plant survival rates, and .hydrocarbon removal efficiencies were investigated over a 4-year period at a site in Somerharju, Luumaki Finland, to assess the remediation potential of the clones. Hydrocarbon content in the soil was determined by gas chromatography and mass spectrometry. The results revealed that hybrid aspen clones 14 and 34 and European aspen clone R3 achieved greater height growth (171, 171, and 114 cm, respectively) than the other clones in the study. Further, the greatest removals of PAH (90% at depth 10–50 cm) and (86% at depth 5–10 cm) were observed in plot G15 planted with clone R2. Furthermore, the greatest TPH removal rate at 5–10 cm depth (C 22 –C 40 , 97%; C 10 –C 40 , 96%; and C 10 –C 21 , 90%) was observed in plot 117 with clone 134. However, other clones demonstrated an ability to grow in soils with elevated levels of TPH and PAH, which indicates their tolerance to hydrocarbons and their potential capacity for phytoremediation of hydrocarbon-polluted soils. Our study suggests that European aspen and hybrid aspen clones could be used for the remediation of soils polluted with PAH and TPH.

Biogeochemical transformation of greenhouse gas emissions from terrestrial to atmospheric environment and potential feedback to climate forcing - Awais Shakoor; Fatima Ashraf; Saba Shakoor; Adnan Mustafa; Abdul Rehman; Muhammad Mohsin Altaf (Environmental Science and Pollution Research, 2020)

Foliar application of gibberellic acid endorsed phytoextraction of copper and alleviates oxidative stress in jute (Corchorus capsularis L.) plant grown in highly copper-contaminated soil of China - Muhammad Hamzah Saleem; Shah Fahad; Muhammad Adnan; Mohsin Ali; Muhammad Shoaib Rana; Muhammad Kamran; Qurban Ali; Inas A. Hashem; Parashuram Bhantana; Mubassir Ali; Reem M. Hussain (Environmental Science and Pollution Research, 2020)

Advances in photo-catalysis approach for the removal of toxic personal care product in aqueous environment - Muhammad Bilal Tahir; Anam Ahmad; Tahir Iqbal; Mohsin Ijaz; Shabbir Muhammad; Saifeldin M. Siddeeg (Environment, Development and Sustainability, 2020)

Heterologous expression of azoreductase-encoding gene azrS of Bacillus sp. MR-1/2 for enhanced azo dye decolorization and wastewater treatment - Ali Abbas; Aqsa Mushtaq; Ayesha Iftikhar Cheema; Faisal Mahmood; Muhammad Asaf Khan; Tahir Naqqash; Mohsin Khurshid; Irfan Manzoor; Sher Muhammad; Muhammad Shahid (Archives of Microbiology, 2020)

Assessing the sustainability of public health in the era of globalization - Mohsin Raza; Muhammad Inam Afzal; Muhammad Ather Elahi (Arabian Journal of Geosciences, 2020)

RETRACTED ARTICLE: Trilemma assessment of energy intensity, efficiency, and environmental index: evidence from BRICS countries - Zulifqar Ali Baloch; Qingmei Tan; Nadeem Iqbal; Muhammad Mohsin; Qaiser Abbas; Wasim Iqbal; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Assessing the integration of solar power projects: SWOT-based AHP–F-TOPSIS case study of Turkey - Muhammad Khalid Anser; Muhammad Mohsin; Qaiser Abbas; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Soil and microbial biomass stoichiometry regulate soil organic carbon and nitrogen mineralization in rice-wheat rotation subjected to long-term fertilization - Muhammad Nadeem Ashraf; Cheng Hu; Lei Wu; Yinghua Duan; Wenju Zhang; Tariq Aziz; Andong Cai; Muhammad Mohsin Abrar; Minggang Xu (Journal of Soils and Sediments, 2020)

Diabetes-associated infections: development of antimicrobial resistance and possible treatment strategies - Muhammad Sajid Hamid Akash; Kanwal Rehman; Fareeha Fiayyaz; Shakila Sabir; Mohsin Khurshid (Archives of Microbiology, 2020)

Analyzing carbon emission transfer network structure among provinces in China: new evidence from social network analysis - Licheng Sun; Lin Qin; Farhad Taghizadeh-Hesary; Jijian Zhang; Muhammad Mohsin; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2020)

Appraisal of wheat genomics for gene discovery and breeding applications: a special emphasis on advances in Asia - Awais Rasheed; Shigeo Takumi; Muhammad Adeel Hassan; Muhammad Imtiaz; Mohsin Ali; Alex I. Morgunov; Tariq Mahmood; Zhonghu He (Theoretical and Applied Genetics, 2020)

Selective cyclooxygenase-2 inhibitors: A review of recent chemical scaffolds with promising anti-inflammatory and COX-2 inhibitory activities - Noor-ul-Amin Mohsin; Muhammad Irfan (Medicinal Chemistry Research, 2020)

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Blood-based gene expression profile of oxidative stress and antioxidant genes for identifying surrogate markers of liver tissue injury in chronic hepatitis C patients - Muhammad Shahid; Muhammad Idrees; Azeem Mehmood Butt; Syed Mohsin Raza; Iram Amin; Afza Rasul; Samia Afzal (Archives of Virology, 2020)

Concomitant Treatment of Tannery and Paper Mill Effluents Using Extremely Metal-Tolerant Sulphate-Reducing Bacteria - Muhammad Muneeb; Muhammad Rashid; Arshad Javid; Syed Mohsin Bukhari; Waqas Ali; Ali Hasan; Muhammad Akmal; Ali Hussain (Environmental Processes, 2020)

Forecasting Nitrous Oxide emissions based on grey system models - Huaping Sun; Jingjing Jiang; Muhammad Mohsin; Jijian Zhang; Yasir Ahmed Solangi (Environmental Geochemistry and Health, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Economics of energy and environmental efficiency: evidence from OECD countries - Robina Iram; Jijian Zhang; Seyfettin Erdogan; Qaiser Abbas; Muhammad Mohsin (Environmental Science and Pollution Research, 2020)

Adaptations in Imperata cylindrica (L.) Raeusch. and Cenchrus ciliaris L. for altitude tolerance - Khawaja Shafique Ahmad; Ambreen Wazarat; Ansar Mehmood; Muhammad Sajid Aqeel Ahmad; Majid Mahmood Tahir; Fahim Nawaz; Haroon Ahmed; Mohsin Zafar; Aneela Ulfat (Biologia, 2020)

Mixed matrix membranes incorporated with sonication-assisted ZIF-8 nanofillers for hazardous wastewater treatment - Mohsin Ali; Muhammad Aslam; Amin Khan; Mazhar Amjad Gilani; Asim Laeeq Khan (Environmental Science and Pollution Research, 2019)

Integrated effect of energy consumption, economic development, and population growth on CO2 based environmental degradation: a case of transport sector - Muhammad Mohsin; Qaiser Abbas; Jijian Zhang; Muhammad Ikram; Nadeem Iqbal (Environmental Science and Pollution Research, 2019)

Evaluating the environmental effects of economic openness: evidence from SAARC countries - Hua-ping Sun; Gulzara Tariq; Muhammad Haris; Muhammad Mohsin (Environmental Science and Pollution Research, 2019)

Economic assessment and ranking of wind power potential using fuzzy-TOPSIS approach - Muhammad Mohsin; Jijian Zhang; Rahman Saidur; Huaping Sun; Sadiq Mohammed Sait (Environmental Science and Pollution Research, 2019)

Estimation of Canal Water Deficit Using Satellite Remote Sensing and GIS: A Case Study in Lower Chenab Canal System - Muhammad Mohsin Waqas; Usman Khalid Awan; Muhammad Jehanzeb Masud Cheema; Ishfaq Ahmad; Matlob Ahmad; Sikandar Ali; Syed Hamid Hussain Shah; Allah Bakhsh; Muhammad Iqbal (Journal of the Indian Society of Remote Sensing, 2019)

Virulence-associated genes and antimicrobial resistance among avian pathogenic Escherichia coli from colibacillosis affected broilers in Pakistan - Mariya Azam; Mashkoor Mohsin; Sajjad-ur-Rahman; Muhammad Kashif Saleemi (Tropical Animal Health and Production, 2019)

Performance of Aeluropus lagopoides (mangrove grass) ecotypes, a potential turfgrass, under high saline conditions - Muhammad Zamin; Abdul Mateen Khattak; Abdul Mohsin Salim; Kenneth B. Marcum; Muhammad Shakur; Shahen Shah; Ibadullah Jan; Shah Fahad (Environmental Science and Pollution Research, 2019)

Forecasting number of ISO 14001 certifications of selected countries: application of even GM (1,1), DGM, and NDGM models - Muhammad Ikram; Amin Mahmoudi; Syed Zulfiqar Ali Shah; Muhammad Mohsin (Environmental Science and Pollution Research, 2019)

Enterobacter sp. strain Fs-11 adapted to diverse ecological conditions and promoted sunflower achene yield, nutrient uptake, and oil contents - Muhammad Shahid; Sohail Hameed; Mohsin Zafar; Muhammad Tahir; Muhammad Ijaz; Mohsin Tariq; Khadim Hussain; Amanat Ali (Brazilian Journal of Microbiology, 2019)

Potentially toxic elements in soil of the Khyber Pakhtunkhwa province and Tribal areas, Pakistan: evaluation for human and ecological risk assessment - Umar Saddique; Said Muhammad; Mohsin Tariq; Hua Zhang; Mohammad Arif; Ishtiaq A. K. Jadoon; Nimat Ullah Khattak (Environmental Geochemistry and Health, 2018)

Mercury contamination in selected foodstuffs and potential health risk assessment along the artisanal gold mining, Gilgit-Baltistan, Pakistan - Arjumand Riaz; Sardar Khan; Said Muhammad; Caihong Liu; Mohammad Tahir Shah; Mohsin Tariq (Environmental Geochemistry and Health, 2018)

Distribution of IL28B and IL10 polymorphisms as genetic predictors of treatment response in Pakistani HCV genotype 3 patients - Humaira Naeemi; Rabia Aslam; Syed Mohsin Raza; Muhammad Aiman Shahzad; Shagufta Naz; Sobia Manzoor; Saba Khaliq (Archives of Virology, 2018)

Assessment of sea water inundation along Daboo creek area in Indus Delta Region, Pakistan - Ibrahim Zia; Hina Zafar; Muhammad I. Shahzad; Mohsin Meraj; Jamil H. Kazmi (Journal of Ocean University of China, 2017)

Genetic Testing of Non-familial Deaf Patients for CIB2 and GJB2 Mutations: Phenotype and Genetic Counselling - Hina Shaikh; Ali M. Waryah; Ashok K. Narsani; Muhammad Iqbal; Mohsin Shahzad; Yar M. Waryah; Naila Shaikh; Amber Mahmood (Biochemical Genetics, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Immobilization of Pb and Cu in polluted soil by superphosphate, multi-walled carbon nanotube, rice straw and its derived biochar - Muhammad Shahid Rizwan; Muhammad Imtiaz; Guoyong Huang; Muhammad Afzal Chhajro; Yonghong Liu; Qingling Fu; Jun Zhu; Muhammad Ashraf; Mohsin Zafar; Saqib Bashir; Hongqing Hu (Environmental Science and Pollution Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

FRET-based genetically-encoded sensors for quantitative monitoring of metabolites - Mohd. Mohsin; Altaf Ahmad; Muhammad Iqbal (Biotechnology Letters, 2015)

Potato Starch as a Coagulant for Dye Removal from Textile Wastewater - Muhammad Shahzad Zafar; Muhammad Tausif; Muhammad Mohsin; Syed Waqas Ahmad; Muhammad Zia-ul-Haq (Water, Air, & Soil Pollution, 2015)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

Interactive effect of cobalt and nitrogen on growth, nodulation, yield and protein content of field grown pea - Fahmida Mir Akbar; Mohsin Zafar; Abdul Hamid; Maqsood Ahmed; Abdul Khaliq; Muhammad Riaz Khan; Zahid ur Rehman (Horticulture, Environment, and Biotechnology, 2013)

A new bivariate Gamma distribution generated from functional scale parameter with application to drought data - Muhammad Mohsin; Albrecht Gebhardt; Jürgen Pilz; Gunter Spöck (Stochastic Environmental Research and Risk Assessment, 2013)

Eggs Distribution Behaviour of Dubas Bug (Ommatissus Lybicus: Homoptera: Tropiduchidae) in Relation to Seasons and Some Physico- Morphic Characters of Date Palm Leaves - Arif Shah; Ata Ul Mohsin; Zahid Hafeez; Muhammad Naeem; Muhammad Irfan Ul Haq (Journal of Insect Behavior, 2013)

Landslide dam and subsequent dam-break flood estimation using HEC-RAS model in Northern Pakistan - Mohsin Jamil Butt; Muhammad Umar; Raheel Qamar (Natural Hazards, 2013)

On the performance of a new bivariate pseudo Pareto distribution with application to drought data - Muhammad Mohsin; Gunter Spöck; Jürgen Pilz (Stochastic Environmental Research and Risk Assessment, 2012)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Synthesis of a New Tri-Branched PEG-IFNα2 and Its Impact on Anti Viral Bioactivity - Muhammad Farooq Sabar; Mustansara Yaqub; Mohsin Ahmad Khan; Nadeem Ahmad; Muhammad Usman Ghani; Mariam Shahid (International Journal of Peptide Research and Therapeutics, 2010)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)